Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 1257590331 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "TaxonKey is Animalia" ] } The dataset includes 1257590331 records from 20976 constituent datasets: 32 records from Antarctic Pycnogonids II. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 9 records from Oberservation of birds at station PS14/143 along 49° West. 1747 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 5437 records from 2020_biodiversity_information_specimen. 2560 records from Upper Silesian Museum, Bird Observations. 147 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 1141 records from Données naturalistes de Quentin ROME. 269 records from SEWBReC Springtails and allies (South East Wales). 13 records from Four new species of Phrynus, Lamarck (Arachnida: Amblypygi) from Mexico. 1 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 62 records from Polychaeta and Oligochaeta of the Auckland and Campbell Islands, New Zealand, 1941-1945. 59 records from Artenvielfalt auf dem Schulgelände. 1431 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2007. 419 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 317 records from National Museum of Natural Science. 165 records from Diversidad de anfibios en tres coberturas vegetales y su relación con actividades antrópicas (amenazas) presentes en el Parque Nacional Natural Tatamá y su área de influencia.. 22 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 484 records from Agencement temporel des populations et des peuplements d'invertébrés benthiques. 69 records from BIRDRACE Pfeifenten. 26 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 42 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 146 records from Données de la naturaliste Laurence Beauchamp. 52 records from Collections ichtyologiques et herpétologiques (BOUM). 78 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 13549 records from Données naturalistes de Bruno OGER. 3 records from A new madicolous species of Nilotanypus Kieffer (Diptera: Chironomidae) from Amazon region, northwestern Brazil. 5 records from First record of the genus Tanaostigma (Hymenopteraı Chalcidoideaı Tanaostigmatidae) from the Afrotropical region with description of three new species. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 18 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 436 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 1015 records from Migration and foraging ecology of Greater Shearwater (aggregated per 1-degree cell). 82 records from Données du/de la naturaliste Swoszowski Florie provenant de la base de donnée du SINP Île-de-France CETTIA. 52 records from Occurrence of mammalia relicts at site Pestera Bursucilor. 1 records from Sarcocheilichthys vittatus, a new species of gudgeon (Teleostei: Cyprinidae) from the Poyang Lake Basin in Jiangxi Province, South China. 6192 records from NE Scotland fish records 1800-2010. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 2 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 33 records from Pollen profile ADR353. 57892 records from Fichier communal des ongulés. 6 records from Sächsische Schweiz (Pfaffenstein). 576 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 37 records from Happywhale - Short-beaked Common Dolphin in North Pacific Ocean. 6 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 25 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 9176 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 110 records from Living Cirripedia. 7 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 112 records from UNCW Norfolk Canyon Aerial Survey - Right side - 2015. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 218 records from Land and freshwater molluscs of Northern Spain. 37 records from Roter Berg Werdau (Leubnitz). 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3775 records from Données naturalistes de Charlotte PICARD. 6 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (PLECHA). 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 4 records from Ostracoda abundance of Hole 44-390. 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 9883 records from University of Nebraska State Museum Birds Collection. 30192 records from University of California Santa Barbara Invertebrate Zoology Collection. 76 records from Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 2 records from Neue Milbenarten aus Kärnten. 2 records from Vietnamella chebalingensis, a new species of the family Vietnamellidae (Ephemeroptera) from China based on morphological and molecular data. 74425 records from Entomology Collection at the Natural History Museum of Utah. 1 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 4882 records from 台灣花蓮沿海賞鯨活動鯨豚觀測紀錄 (The observation records from the activities of whale and dolphin watching in the offshore of Hualien, Eastern Taiwan). 40 records from makran-chabahar-arthropods. 3 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 602 records from NMML Small Cetacean Aerial Survey 1997. 137 records from Hartland Nature Club Lepidoptera Collection. 114 records from BIRDRACE LiLaLau. 80311 records from Fish specimens of Kagoshima University Museum. 112 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 3820 records from UTEP Invertebrates (Arctos). 1308 records from Fish occurrence in Kuban River basin. 26 records from Schulteich Freie Waldorfschule Darmstadt. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 10 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 11 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 22052 records from CNIN/Abejas de México/Apoidea. 614 records from MGYS00005313. 145 records from Fototrampeo al interior de las áreas del Banco de Hábitat del Meta de Terrasos. 181 records from UNCW Norfolk Canyon Aerial Survey - Left side - 2016. 7 records from Revision of Chaetacanthus Seidler, 1922 (Annelida, Phyllodocida, Polynoidae). 3510 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 876 records from Ensemble des données Odonates. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 2034 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 3 records from Mangelia (Gastropoda, Conoidea) species of the Turkish coasts with description of Mangelia vanaartseni sp. nov.. 1 records from Happywhale - Green Sea Turtle in North Pacific Ocean. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 10 records from Ostracod species in Oligocene sediments of core CRP-3. 2194 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 2997 records from MMS Seabird Ecology Study 1985. 1422 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 47 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 12 records from Art´n Vielfalt im Kinderwald. 38 records from Ours 2006 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 14 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 50 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 287 records from UF Environmental Archaeology Tick Island Zooarchaeological Data. 18 records from Phase 2 Lowland Grassland Survey of Wales. 234 records from Invasive Non-Native Species, Outer Hebrides. 11 records from Benthic macrofauna abundance of sediment core 13077-093. 267172 records from hymenoptera. 1588 records from Naturalis Biodiversity Center (NL) - Crustacea. 4193 records from Leicestershire and Rutland Aculeate Records. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 7 records from First record of the genus Agnara (Isopoda: Oniscidea) from Iran with descriptions of two new species. 25 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 16618 records from Suivi Temporel des Libellules (STELI). 1 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 2711965 records from First Bird Atlas. 656 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 2 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 2 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 1 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 1 records from Reptilia ZMK. 1905 records from MMS Marine Mammal Survey, PNW 1989-1990. 70 records from Ensemble des données Orthoptères. 1290 records from Diversity of Spiders from Azorean Trails. 13442 records from United Kingdom National Whale Stranding Database 1913-2008. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 69 records from Pollen profile RAC20, Lake Racou, France. 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 44 records from Oman 2008: Olive Ridley Turtles of Masirah (aggregated per 1-degree cell). 11 records from A New Perlodes Species And Its Subspecies From The Balkan Peninsula (Plecoptera: Perlodidae). 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 90 records from Natura 2000 Vallée de la Seille. 10283 records from Inventario de Hymenóptera; parasítica en México. 989 records from Programme ACT : Répartition Pigeon ramier 2006 - 2010 Coordonnées GPS Lambert 93. 8561 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 3 records from 3Soil16S. 792 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases: Cliff-nesting Birds, priority conservation species: Complementary Observations - [2010-2014]. 2 records from Early myriapodous arthropods from Australia: Maldybulakia from the Devonian of New South Wales. 1285 records from Suivi des aires marines protégées de Moorea - Invertébrés benthiques. 288 records from Sea Turtles of Dominica (aggregated per 1-degree cell). 4 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 4 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 14 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 2 records from Analyses of the recent components of sediment core PS1277-1. 24645 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 15 records from Inventaire des mammifères du Parc de la Haute-Île (93). 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 47 records from Waldstück Bremerhagen LK Bio Kl. 12. 9 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 108 records from MIRC NAVFAC Incidental Sightings - Aerial 1965-2014. 32 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 235 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 138 records from A review of the Glossogobius giuris complex in Australia, with wider discussion on nomenclature and possible synonymies. 58 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 4 records from Range table from benthic foraminifers in ODP Hole 146-889A. 138 records from Bannwald Burghauser Forst. 11 records from New England Aquarium Harbor Porpoise Tracking (aggregated per 1-degree cell). 948 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 290 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 25473 records from SEWBReC Bees, Wasps and Ants (South East Wales). 366 records from UCSC Elephant Seals (aggregated per 1-degree cell). 54 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 20 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 13 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 8 records from HRC Koa Kai Marine Species Monitoring Vessel Surveys November 2010. 2127 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 10 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 77 records from Sorensen distance for herbivores. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 4 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 19013 records from University of Guam Insect Collection. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 2 records from Dermaptera of Iran with description of Euborellia angustata sp. nov.. 3 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 30 records from Artenvielfalt des "Grünen Klassenzimmers". 605 records from Zoocenosis of the mole burrows in the forest zone of Western Siberia. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 1 records from A Scanning Electron Microscopy Study Of The Epiprocts Of Western North American Sweltsa (Plecoptera: Chloroperlidae). 44 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 167 records from AMAPPS Southeast Aerial Cruise Fall 2016. 1 records from First record of Orthelimaea himalayana (Ingrisch, 1990) (Orthoptera: Tettigoniidae: Phaneropterinae: Elimaeini) from India with description of its female. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1189 records from UWIZM Molluscs. 5 records from Inventaire biodiversité du site Pierre Fabre d'Aignan. 4073 records from MCP-Aves - Coleção de Aves. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 100 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 371 records from orthopteracollections-nhmj-ioj. 778 records from Bird specimens of Saitama Museum of Natural History. 2 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 42 records from Inventaire des Octocoralliaires des fonds sédimentaires de la région niçoise. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 34 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 9120 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 1 records from Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand. 173 records from UWIZM Anoles. 7 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 59 records from Pollen analysis of sediment profile TR0 from Truennensee. 2203 records from Macrobenthos Chukchi Sea, 1986. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 20 records from Condamine Alliance. 9 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 6 records from Comparative study in validity of three regions of 18S-rRNA for eukaryote amplicon sequence analyses. 367 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 15 records from Tardigrad collection of the National Museum of Nature and Science. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 4 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 748 records from AMAPPS Northeast Aerial Cruise Summer 2010. 21 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 27 records from Faunal assemblage of sediment core TR149-31. 2 records from Microbial community in marine sediments. 599 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 18 records from Naturtag. 8 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 17 records from données espèces - Expertise IPE 63. 88 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 59 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 41 records from HRC CRC Small Vessel-Based Monitoring Surveys July 2006. 160408 records from Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 1 records from A new Rhopalomeris species (Diplopoda: Glomerida: Glomeridae), and notes on the phylogenetic relationships between glomeridans in Vietnam. 26 records from Chaoborus flavicans Meigen (Diptera, Chaoboridae) is a complex of lake and pond dwelling species: a revision. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 3 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 12 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 2 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 34 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 7283 records from Colecção Entomológica IIA. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 16763 records from MZFC/Coleccion de Aves. 1190 records from Coleópteros presentes en un proceso de restauración pasiva en bosque seco tropical. 24 records from Dubai Turtle Rehabilitation Project (aggregated per 1-degree cell). 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 1070 records from DMNS Egg Collection (Arctos). 1 records from Happywhale - Layard's beaked whale in Southern Ocean. 13203 records from Lepidopterous specimens of Yamagata Prefectural Museum. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 2007 records from Happywhale - Humpback Whale in Arctic Ocean. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 93 records from UNCW Hatteras Aerial Survey - Right side - 2015. 7 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 193 records from The diversity of the genus Aricidea (Polychaeta: Paraonidae) from the Sea of Marmara, with descriptions of two new species and two new records for the Mediterranean fauna. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 5405 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 987 records from Orthoptera - SMF. 26 records from HRC USWEX Aerial-Based Monitoring Surveys 2007. 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 287870 records from Florida Keys Reef Visual Census 2014. 59 records from Visual and genetic surveys for odontocete cetaceans in American Samoa 2003-06. 15 records from A practical introduction to microbial molecular ecology through the use of iChips. 2 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 957 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 1 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 1011 records from SCANS II cetacean sightings on primary platform of vessel surveys 2005. 592 records from Colección de Entomología - Curculionidae. 710 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 6 records from Validation of Stenus (Hypostenus) primivenatus and Stenus (Hypostenus) yiae (Coleoptera, Staphylinidae, Steninae). 1 records from marine sediment metagenome Raw sequence reads. 13 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 776 records from Programme ACT : Répartition Pie bavarde 2010 - 2014 Coordonnées GPS Lambert 93. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 1 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 22157 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 6230 records from Plecoptera. 5 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 9 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 5 records from New Species Of Neoperla Needham And Phanoperla Banks (Plecoptera: Perlidae) From The Philippine Islands. 10 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 184 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 12 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 14 records from NZCS Brownsberg Nature Park Monitoring. 981 records from Bees in the UVM Zadock Thompson Zoological Collection. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 61674 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 66 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 35 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 20 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 120 records from BIRDRACE The early birds. 39 records from Huangilene, a new genus for the Miltochrista alikangiae (Strand, 1917) species-group, with descriptions of three new species from Indochina, continental China and Taiwan (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 2 records from Description of a new species of Cosmocerca Diesing, 1861 (Nematoda Cosmocercidae) in Hoplobatrachus crassus (Jerdon, 1853) (Anura: Dicroglossidae from Asansol coal-field area, West Bengal, India. 1933 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 16 records from Sunshine Coast Council Turtle Tracking (aggregated per 1-degree cell). 69 records from Ours 2010 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 50076 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 1289 records from RECORD Orthoptera Data. 715 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 9 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 76 records from BIRDRACE Nachtigallen. 1573 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 1284 records from ConDidact Citizen Science Surveys - Amphibians 2007. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 13 records from Données naturalistes de THÉVENOT Jessica. 250 records from Deep Sea fishes (Chondrichthyes, Osteichthyes) in the Southwestern Colombian Caribbean. 155 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 27 records from Occurrence of mammalia relicts at site Biedermann. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 25 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 678 records from Lucanidae. 29 records from New species, synonymy and records of Endomia and Stenidius (Coleoptera: Anthicidae) from Asia. 27670 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 276 records from Birds Specimens of Akita Prefectural Museum. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 19 records from Données naturalistes de LE GLOANEC Vincent. 177831 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-78. 41 records from MSUM Ichthyology and Herpetology Collections. 3 records from Epiproct And Dorsal Process Structure In The Allocapnia Forbesi Frison, A. Pygmaea (Burmeister), And A. Rickeri Frison Species Groups (Plecoptera: Capniidae), And Inclusion Of A. Minima (Newport) In A New Species Group. 14 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 5260 records from Whale catches in the Southern Ocean. 10 records from Benthic macrofauna abundance of sediment core 13200-008. 41 records from Lynx 1999 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 4 records from The fossil avifauna of the tar seeps Las Breas de San Felipe, Matanzas, Cuba. 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 18308 records from River Biologists' Database (EPA). 803 records from Great Eastern Ranges - Slopes to Summit. 230 records from Biometría peces Parque Nacional Natural La Paya. 75 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 97119 records from Tiroler Landesmuseum Ferdinandeum. 4 records from Seven species of Pseudopecoeloides Yamaguti, 1940 (Digenea, Opecoelidae) from temperate marine fishes of Australia, including five new species. 91 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 13846 records from Données faune Nature 18 - 2017. 54 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 8851 records from Odonata records from RSPB Reserves 1970-2009. 855 records from Données supplémentaires Atlas des Mammifères marins. 53 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 9 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 1 records from Bryozoans Specimens of Akita Prefectural Museum. 18 records from Anfibios presentes en el Cerro Jánano. 26 records from Données espèces - Expertise IPE 79. 2 records from Two new species of the genus Malayepipona Giordani Soika (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with updated key to all recognised species. 1591319 records from NBIS Records to December 2016. 128 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 24 records from Happywhale - Risso's Dolphin in North Atlantic Ocean. 1 records from Thraulodes marianoi sp. nov., a remarkable new species of mayfly (Ephemeroptera Leptophlebiidae) with dark wings from the southern Brazilian Atlantic Forest. 2642 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 688 records from South American Antarctic Marine Biodiversity Literature. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 1 records from Tibetyrus gen. nov., a new myrmecophilous Tyrini from Xizang, China (Coleoptera: Staphylinidae: Pselaphinae). 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 81 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 5 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 35 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 286 records from California State University, Long Beach Birds. 1926 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 22 records from Ostracoda abundance of Hole 24-238. 4 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 15 records from Meiofauna abundance in sediment core 54301-010. 713 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 141 records from Collection Hydrozoa - ZSM München. 558 records from SOCAL FZN4 Marine Mammal Aerial Monitoring 2013. 777 records from Happywhale - Leopard seal in Southern Ocean. 3345 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 9055 records from NE Scotland other invertebrate records 1800-2010. 21 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 25 records from Base de données en ligne d'observations naturalistes de mammifères marins. GEPOG & LPO. 43 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 125 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 98 records from Données opportunistes sur les odonates. 14903 records from Données Entomologiques A. HORELLOU 1988-2018. 12 records from 2017 Onwards Rare Invertebrates in the Cairngorms Shining Guest Ant Survey Data. 5 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 2 records from A new species of Paralithoxus (Siluriformes: Loricariidae: Ancistrini) from the highlands of Serra da Mocidade, Roraima State, Brazilian Amazon. 7 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 284 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Rediscovery of Glenurus incalis Banks (Neuroptera: Myrmeleontidae), and notes on the Brazilian species of Glenurus Hagen. 243 records from Antarctic Amphipoda. 49 records from Lebensraum Gesamtschule (Langerwehe). 13 records from Foraminifera abundance of Hole 64-481. 5 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 2 records from Two remarkable new species of oribatid mites (Acari: Oribatida) from Acacia litter of Kerala, India. 76 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 905 records from Coléoptères Silphidés du département du Loiret. 409647 records from NOAA AFSC North Pacific Groundfish Observer. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 24 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 2380 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 177 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 16 records from Hazel Dormouse in Ireland. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 1027 records from Programme ACT : Répartition Merle noir 1996 - 2000 Coordonnées GPS Lambert 93. 946 records from NW Pacific Deep-sea Benthos Biodiversity (Beneficial Project). 7 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 647 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 52610 records from Insects, Outer Hebrides. 33 records from An der Ohm, (Wettsaasen). 8 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 185 records from Inventaire des odonates d'intérêt communautaire. 477 records from Philippine Mollusk Symbiont - ICBG Collection. 3 records from Manx Basking Shark Watch 2017-2018 (aggregated per 1-degree cell). 149 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 1889 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 13527 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 6 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 11080 records from BLM CETAP AIR Sightings. 2920 records from Collections of Bioclass, school #179, Moscow. 5 records from Microbial community structure and dynamics in the oxygen minimum zone of the Northeast subarctic Pacific Ocean. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 54550 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2016. 1818 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 225 records from AFTT JAX Aerial Survey -Left side- 2014. 60 records from Amphibian and Reptilian (KIEE-AR). 4 records from Cast netting new species: Integrative taxonomy of Distichodus notospilus (Characiformes: Distichodontidae) discovers new species and overlooked areas of endemism in Central Africa. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 325 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 3 records from A new species, a new combination, and a new record of Crossotarsus Chapuis, 1865 (Coleoptera, Curculionidae, Platypodinae) from China. 1 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 1166 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 11 records from Hawksbill turtles in Torres Strait (aggregated per 1-degree cell). 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 150365 records from Leicestershire and Rutland Environmental Records Centre records 2015-2019. 1043409 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 413272 records from DATAVES. 23 records from Herpetofauna asociada a la cuenca del río Quito - Chocó, 2014. 11 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 3 records from Oxynoemacheilus shehabi, a new nemacheilid loach from the upper Orontes in southern Syria (Teleostei: Nemacheilidae). 249 records from Fermanagh Flora. 74002 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 58 records from Isle of Wight non-native invasive species. 2 records from Transfer of two South American ant species from Tapinoma Foerster 1850 to Forelius Emery 1888 (Hymenoptera: Formicidae: Dolichoderinae). 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 22 records from Description of Bagarius vegrandis, a new species of sisorid catfish from Indochina (Actinopterygii: Siluriformes), with notes on the identity of Bagarius bagarius. 4 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 78 records from Données de la naturaliste Anna Even. 4 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 11 records from Happywhale - Peale's Dolphin in South Atlantic Ocean. 553 records from Molecular phylogeny of the genus Lasiopogon (Diptera: Asilidae) and a taxonomic revision of the bivittatus section. 21 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 60 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 368 records from UNCW Aerial Survey 1998-1999. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 29 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 5 records from Die Bachspezies 2008/2009. 73 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 1 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 3 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 45065 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 1252 records from Censos de aves en los municipios de Honda (Tolima) y Guaduas (Cundinamarca) - Reexpedicion Chapman. 5 records from Streuobstwiese. 23 records from Abundance of benthos infauna at station GIK23042-2. 746261 records from Western Australian Museum provider for OZCAM. 43 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 445 records from Colección de mamíferos voladores y no voladores de la Universidad de Nariño. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 1 records from Description of a new species of the Melanorivulus pictus species-group (Cyprinodontiformes: Rivulidae) from the Rio Paraná basin in Brazil. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 79750 records from NRW Regional Data: South East Wales Non-sensitive species. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 47 records from Marine Turtle Conservation Project 2012-2013 (aggregated per 1-degree cell). 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1009 records from Programme ACT : Répartition Merle noir 2012 - 2016 Coordonnées GPS Lambert 93. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 20 records from Waldstück am Schullandheim Bad Bederkesa. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1461 records from M. Gollop Collection. 334 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 140 records from Naturalis Biodiversity Center (NL) - Diptera. 1 records from Données naturalistes d'Olivier DELZONS. 19 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 174 records from BIRDRACE Bon(n)apartemöwen. 10 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 1 records from A new aquatic beetle family, Meruidae, from Venezuela (Coleoptera: Adephaga). 17 records from Plant-parasitic nematodes of Republic of Karelia. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 101 records from Lynx 2002 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 1 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 3 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 5 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 521 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 21 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 38 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 212256 records from University of Minnesota Insect Collection. 16 records from Insect Collections of Okomu National Park- Nigeria. 215 records from Heinersdorfer Sumpfwiese. 133637 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 279489 records from ARABEL - Arachnologia Belgica. 8 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 8 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 1 records from Capnia Shasta, A New Species In The Californica Group From Northwestern California (Plecoptera, Capniidae). 22176 records from Arctic Species Trend Index (ASTI) : Marine. 1 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 7 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2). 33409 records from Wolli Creek Preservation Society Bird Survey. 348 records from Antarctic pycnogonids. 60961 records from MLZ Bird Collection (Arctos). 5 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 14 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 31 records from Naturschutzgebiet Müchelholz (Mücheln). 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 5 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 31 records from Wiese am Waldrand (Gurtweil). 403 records from NMML Gulf of Alaska marine mammal survey 2003. 9120 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 39 records from Northern Cyprus 2010 (aggregated per 1-degree cell). 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 147049 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 385 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 7 records from Happywhale - Leatherback Sea Turtle in North Pacific Ocean. 279 records from Atlas des Hyménoptères Pompilidae du Massif armoricain et des départements voisins : prospections 2018. 6672 records from Midden-Limburg Fish Ponds Survey. 4 records from A remarkable new species of Micropeza Meigen (Diptera: Micropezidae) from Caatinga biome, Brazil. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 5 records from Herbarium Senckenbergianum (FR) - Fungi. 1994 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 6478 records from National System of Protected Areas in Poland - Animals. 11 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 5 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 1819 records from AMAPPS Northeast Aerial Cruise Summer 2016. 895 records from Geometridae de France métropolitaine. 18 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 4 records from Review the bamboo-feeding genus Arcofaciella Fennah, 1956 (Hemiptera: Fulgoromorpha: Delphacidae) with description of a new species from India. 8 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 259 records from Programme ACT : Répartition Alouette lulu 2009 - 2013 Coordonnées GPS Lambert 93. 1 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 115 records from Israel Sea Turtle Tracking Project 2008: Loggerhead & Green Turtles (aggregated per 1-degree cell). 3 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 1 records from Acantorna-a new genus of Hymedesmiidae (Porifera, Demospongiae Poecilosclerida) from the western Aleutian Islands of Alaska with description of Acantorna tahoma n. sp.. 3 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 2 records from A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India. 2 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 6916 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 16838 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 31 records from HRC SCC Vessel-Based Monitoring Surveys February 2010. 3 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 75 records from Happywhale - Bryde's whale in South Atlantic Ocean. 111 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 2 records from The first species of the pseudoscorpion genus Lechytia Balzan, 1892 (Pseudoscorpiones, Chthoniidae) from New Zealand. 5 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 121 records from Registros de dípteros asociados al proyecto: Estratificación espacial del dengue basado en la identificación de factores de riesgo en el departamento del Cauca. 2781 records from Marine Turtles. 670 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 81 records from Gabon 2009-10: Pongara, Leatherback Turtles (aggregated per 1-degree cell). 240 records from Evaluación del macrobentos de la plataforma continental del Caribe colombiano. 5 records from The species of the bee genus Centris of the “ hyptidis group ” revisited with the description of Centris (Anisoctenodes) new subgenus (Hymenoptera: Apidae: Centridini). 1 records from Description of a new species of Megischus Brulle (Hymenoptera, Stephanidae), with a key to the species from China. 783 records from Programme ACT : Répartition Tourterelle des bois 2011 - 2015 Coordonnées GPS Lambert 93. 454 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 6 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 1298 records from Vermont Orthoptera Records from Historic Dot Maps. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 3927 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 2 records from Colección de Bacterias del Museo de Historia Natural Marina de Colombia – Makuriwa (Invemar). 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 6 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 417 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 4 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 7 records from New species of Culex (Culiciomyia) (Diptera: Culicidae) from Talangaye Forest in Cameroon and descriptions and identification keys for males of the Afrotropical species of the subgenus. 175 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 34 records from Naturgrundstück (Eutin). 11896 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 11 records from SNI California Sea Lions 2014 (aggregated per 1-degree cell). 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 229 records from données araneologiques de LEENKNEGT Virginie. 20 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 68907 records from Données de l'Observatoire de la Faune de Bourgogne. 46 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 255 records from Programme ACT : Répartition Perdrix rouge 2009 - 2013 Coordonnées GPS Lambert 93. 4389 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 677 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 5 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 539 records from Phenological Center - Birds (Murmansk). 100 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 1 records from Microbial diversity studies of Arabian Sea sediment. 67 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 197 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 320 records from Echinoderms from the Seaflower Biosphere Reserve. 198 records from Programme ACT : Répartition Alouette lulu 1996 - 2000 Coordonnées GPS Lambert 93. 3 records from A review of the genera Anasillomos Londt, 1983, Oratostylum Ricardo, 1925, and Remotomyia Londt, 1983, with description of a new genus and two new species (Diptera: Asilidae: Stenopogoninae). 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 4 records from Analyses of the recent components of sediment core PS1011-1. 368 records from Biological Recording in Scotland - Bumblebee Survey. 1 records from Allan Herbarium (CHR). 68459 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 24 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 16 records from Two new sympatric species of Stenocercus (Squamata: Iguania) from the inter- Andean valley of the Mantaro River, Peru. 1124 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 30 records from MVZ Herp Observations (Arctos). 154 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 23 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 205 records from CRC HRC Shore-based Surveys KB11 2013-2015. 1 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 987 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 250 records from Données naturalistes d'Olivier LAURENT. 2147 records from Restauración y conservación de Isla Guadalupe. 13 records from Coleção de Coleoptera da Universidade de Brasília. 5044 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 22 records from Site Condition Monitoring of dragonflies on Loch aí Mhuilinn SSSI potential extension - 2016. 5 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 20 records from New data on the fauna of China, part I: the taxonomy of the millipede family Julidae (Diplopoda). 310070 records from Seasearch Marine Surveys in England. 61638 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 53 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 9 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 38 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 57 records from Swiss Occurrence Records of Native Species of Various Faunal Groups. 2963 records from Collection Trichoptera - SMF. 6 records from Happywhale - Arnoux's Beaked Whale in Southern Ocean. 93 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 16 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 132 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 184 records from Occurrence of mammalia relicts at site Raj Cave. 64 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 137004 records from Arizona State University Hasbrouck Insect Collection. 63364 records from CCAMLR historic KRILL. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 3361 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 35 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 156 records from Chironomid remains in the sediment sequence of Site PG1212. 8 records from Abundant box jellyfish, Chironex sp. (Cnidaria: Cubozoa: Chirodropidae), discovered at depths of over 50 m on western Australian coastal reefs. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 3 records from Happywhale - Adelie Penguin in Southern Ocean. 87546 records from MDFRC macroinvertebrate survey. 179 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 17 records from Amtsrain Apolda-Zottelstedt. 1 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 8260 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 742 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 1592 records from The Broward College Insect Collection. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 3 records from Supplementary Illustrations For Two Nemoura (Plecoptera: Nemouridae) Species. 41 records from NEON Biorepository Zooplankton Collection (DNA Extracts). 9583 records from Ecosphère_2017_12_18. 48 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1516 records from Records of Halicarcinus planatus at sub-Antarctic regions. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 25 records from New records of Stenopygium Becker (Diptera: Dolichopodidae) from the Neotropical Region, and a key to species. 4479 records from Iowa State University Fishes Collection. 315 records from EDIT - ATBI in Gemer area (Slovakia). 8 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 22114 records from Global compendium of Aedes albopictus occurrence. 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 325 records from Inventaire malacologique de la RNR des Marais de Stors. 39 records from Teich Berlin Wuhlheide. 69 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 2 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 5 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 17 records from AKG-Gelände (Bensheim). 1 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 1 records from Occurrence of mammalia relicts at site Raagelund. 3 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 4602 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 84 records from Ostracoda abundance of Hole 48-403. 79 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 34 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 10699 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 1121 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 20004 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 2714 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 35 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 94 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 31 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 128 records from Inventaire des reptiles 2014. 457 records from MoJ BioBlitz August 2018. 1 records from A new species of genus Oxytauchira from India (Orthoptera: Acrididae). 589 records from Programme ACT : Répartition Pie bavarde 2005 - 2009 Coordonnées GPS Lambert 93. 53 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 40 records from A New Species Of Isoperla Banks (Plecoptera: Perlodidae) From The Southern Appalachians, With Notes On The I. Montana Group. 6 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 29412 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 1 records from West Palaearctic species of the genus Diostracus Loew, 1861 (Diptera: Dolichopodidae). 105 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 55 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 39 records from Dorfrand Mauderode. 411 records from SuLaMa reptile survey I 2012. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 61 records from Shrews of Poland. 2 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 18 records from Bonaire Turtle Tracking 2012 (aggregated per 1-degree cell). 17321 records from K-State Museum of Entomological and Prairie Arthropod Research. 4 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 92 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 28062 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 186 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 3 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 31 records from STELI 2015 Saint-Pée-sur-Nivelle (64) par l'association EcoGIS. 181190 records from Marine benthic dataset (version 1) commissioned by UKOOA. 5229 records from European Moth Nights. 5665 records from The Dolphin Project. 172 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 6759 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 1267 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 12 records from A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes: Heptapteridae) from the Orinoco River basin. 25 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 12 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 1 records from MfN - Micropaleontology. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 296 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 513 records from BUND - Dassower See (Lübeck/Dassow). 4 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 63 records from Birds and plant species near Petushki town (Vladimir region). 58738 records from Données naturalistes de Monsieur François FOURNIER. 2 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 9 records from Jeu de données convention FEGVE-SPN (numéro 2). 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 2 records from Sächsische Schweiz (Wehlener Gebiet). 4 records from Two new species of the genus Deltomerodes Deuve, 1992 (Coleoptera, Carabidae, Patrobini) from Xizang, China. 1 records from Coarazuphium lundi (Carabidae: Zuphiini), a new Brazilian troglobitic beetle with the designation of a neotype for C. pains Álvares & Ferreira, 2002. 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 66 records from Appendicularia abundance of station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 1). 29 records from Ours 2004 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 962 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 6042 records from Arthur Chapman Observations. 303 records from Cuxhavener Küstenheiden. 1 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 2523 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 1451634 records from Hatikka Observation Database. 337 records from Données naturalistes de Monsieur JOURDE Rémi. 873 records from Programme ACT : Répartition Geai des chênes 2008 - 2012 Coordonnées GPS Lambert 93. 125114 records from inatura - Erlebnis Naturschau Dornbirn. 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 35 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 4 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 93 records from ProDelphinus Peru Leatherback Tracking Project (aggregated per 1-degree cell). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 20 records from (Table 2) Stratigraphic occurrence of selected diatom species from DSDP Hole 12-112. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 302 records from New data on species diversity of Annelida (Oligochaeta, Hirudinea) in the Kharbey lakes system, Bolshezemelskaya tundra (Russia). 5 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 8 records from Benthic macrofauna abundance of sediment core 13078-015. 129 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 95 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 5478 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 238 records from Données Mammifères marins Aquasearch - Dauphin Passion. 3 records from Parochodaeus bituberculatus (Erichson) (Coleoptera: Ochodaeidae) and Faargia gentilii (Martínez) (Coleoptera: Scarabaeidae), two species newly discovered in Chile. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 6213 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2009. 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 749 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 10075 records from Nematoda of Costa Rica (INBio). 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 1494 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 4 records from Two more new species of the Cyrtodactylus peguensis group (Squamata: Gekkonidae) from the fringes of the Ayeyarwady Basin, Myanmar. 9084 records from WTSWW Data: All Taxa (West Wales). 612 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 2318 records from Données naturalistes de Bernard Lalanne-Cassou. 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 7 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 1402 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 446 records from Programme ACT : Répartition Etourneau sansonnet 2006 - 2010 Coordonnées GPS Lambert 93. 3327 records from BioGIS - Mammals - SPNI. 21 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 25864 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 510 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 6 records from Four new species of Scydmaeninae and Pselaphinae (Coleoptera: Staphylinidae) from Yunnan, China. 933265 records from SEWBReC Birds (South East Wales). 39903 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 807 records from Área Galeras - Monitoreo de Aves, 2016. 7606 records from Lepidoptera of Mordovia State Nature Reserve. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 321 records from Collection Echinodermata SMF. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 5860 records from MfN - Fossil vertebrates IV. 5020 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 22 records from The fishery ground near Alexandria. XVI. Cumacea, stomatopoda, leptostraca by Adolf Steuer (1938).Notes and Memoirs No 26.. 102 records from Rainforest and cloud forest Scolytodes (Curculionidae, Scolytinae, Hexacolini) from the Arthropods of La Selva inventory in Costa Rica: new species, new synonymy, new records. 15 records from Suivi de la colonie de Pipistrelles de la Petite Ceinture à Paris. 21 records from Riedkanal Bötzingen. 1 records from New record of the genus Baetiella Uéno, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 54 records from Aves marinas del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 58 records from Données du/de la naturaliste Williamson Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A new record of the family Isonychiidae (Insecta: Ephemeroptera) from the Western Ghats, India with a description of new species. 5 records from Seven new species and additional records of Palaearctic Leptusa, primarily from Yunnan, China (Coleoptera: Staphylinidae: Aleocharinae). 2 records from The first record of the family Chloroperlidae (Plecoptera) from the Guangxi Zhuang Autonomous Region of southern China, with description of a new species of Sweltsa Ricker, 1943. 3 records from TWO NEW SPECIES OF ORIPODOIDEA (ACARI: ORIBATIDA) FROM VIETNAM Sergey G. E and Alexander E. A. 124 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 6 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 6 records from Wuhle - Brücke / B1. 26 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 27 records from CNMI Sea Turtle Program satellite tracked green turtles 2011. 2 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 2 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 5 records from Compost microbe establishment and growth in agricultural soils. 202122 records from National Benthic Inventory. 20 records from Bostryx tortoranus (Doering, 1879) species complex (Gastropoda: Stylommatophora: Bulimulidae), a review of taxonomy and distribution of endemic species from Argentina. 16 records from Phenological Center - Fishes (Murmansk). 111 records from BIRDRACE Die Wendehälse. 63 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 172 records from SEFSC GoMMAPPS Vessel Survey 2018 Summer. 3 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 8332 records from Scotland Otter Survey Database. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 1037 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 1486 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 36 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 89987 records from CAS Entomology (ENT). 6087 records from Naturalis Biodiversity Center (NL) - Pisces. 177918 records from Carnet B Lorraine. 27 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 445 records from Oceanic Society's Marine Mammal Sightings in Belize 1992 - 2011. 8 records from Revision Of The Australian Coccinellidae (Coleoptera). Genus Novius Mulsant Of Tribe Noviini. 11163 records from Programme FLASH : Répartition Pigeon ramier 2012 - 2016 Coordonnées GPS Lambert 93. 1621449 records from Dragonfly records from the British Dragonfly Society Recording Scheme. 2 records from A new species of Hypsohapsis (Heteroptera: Schizopteridae: Hypselosomatinae) from the Brazilian Amazon. 61 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes (Crustáceos). 18 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 13 records from Records Of Neoperlini (Plecoptera: Perlidae) From Brunei Darussalam And Sarawak, With Descriptions Of New Phanoperla Banks And Neoperla Needham Species. 6 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 1 records from Happywhale - Indian Ocean bottlenose dolphin in Indian Ocean. 4 records from A Catalogue and Historical Study of the Odonata of Ecuador. 1361 records from Códigos de barras de la vida en peces y zooplancton de México. 10 records from Description of six new large species of Argentinomyia Lynch-Arribalzaga, 1891 and redescription of Talahua fervida (Fluke, 1945) (Diptera, Syrphidae, Syrphinae). 4 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 1 records from A new species of Casmaria H. Adams & A. Adams, 1853 (Gastropoda, Cassidae) from the Philippines identified by molecular data. 4 records from Loricifera - SMF. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 479121 records from KTP Ring Data. 1 records from Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru. 583 records from Colección Ornitológica-Museo de Historia Natural Unillanos. 4 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 20 records from Subspecies of Pleurota bicostella (Clerck, 1759) revisited and descriptions of nine new species in the P. bicostella species group (Lepidoptera: Gelechioidea Oecophoridae: Pleurotinae). 2252 records from Synthèse de la Répartition des populations de cerf élaphe en 2000 (réseau Ongulés sauvages ONCFS-FNC-FDC). 16439 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 11 records from Données d'observation opportunistes collectées durant la campagne de prélèvements sédimentaires SHELL/CREOCEAN en Guyane française en 2013. Shell Exploration and Production France. 1109 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 1 records from World catalogue of the Hydrophiloidea (Coleoptera): additions and corrections II (2006 - 2010). 1 records from Two new genera and species of Fidicinini Distant, 1905 with a re-description of Nosola Stål, 1866 (Hemiptera, Auchenorrhyncha, Cicadidae). 1 records from The identity of Parandra laevis Latreille, 1804 and nomenclatural changes in the Parandrinae (Coleoptera, Cerambycidae). 41 records from Morphologische Daten von Natrix. 1478 records from Programme FLASH : Répartition Pluvier doré 2012 - 2016 Coordonnées GPS Lambert 93. 21 records from Soil metagenome from healthy and unhealthy agricultural soil. 3 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 2 records from New state and island records of Coccinellidae (Coleoptera) in Hawai‘i, USA. 46 records from Revision of the Garra species of the Hajar Mountains in Oman and the United Arab Emirates with the description of two new species (Teleostei: Cyprinidae). 57 records from Brown University Herbarium. 689 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 89 records from Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 95 records from BIRDRACE accipiter hardcore birding. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 71 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 23 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 1 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 17 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 1 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 118975 records from Happywhale - Humpback Whale in North Pacific Ocean. 695 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 309 records from CNAC/Coleccion Nacional de Acaros. 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 2173 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 229 records from Distribución y estructura poblacional de la tortuga de Berlandier, (Gopherus [=Xerobates] berlandieri) en México. 628 records from hauterivian_echinoids_of_the_paris_basin. 136 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 14 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 179 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 1 records from A new cave-dwelling Gekko (Gekko) from Lopburi Province, central Thailand (Squamata, Gekkonidae). 137 records from BioAcoustica: Wildlife Sounds Database. 8 records from The millipede genus Tylopus Jeekel, 1968 (Diplopoda, Polydesmida, Paradoxosomatidae), with a key and descriptions of eight new species from Indochina. 3 records from Otacilia fansipan spec. nov., the second congener recorded from Vietnam (Arachnida: Araneae: Phrurolithidae). 7 records from TransForest - vegetation, lichen and fungi data 2016. 5 records from INVESTIGATING THE MICROBIAL EUKARYOTIC COMMUNITIES IN THE SURFACE WATERS OF THE ARAFURA SEA AND CORAL SEA. 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 1 records from A new species of Liphistius from Myanmar and description of the actual male of L. birmanicus Thorell, 1897 (Araneae, Mesothelae, Liphistiidae). 126 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 14 records from CEFS_16S_ITS. 17892 records from Biowide Species data. 11 records from Inventaire et regroupement de données Natura 2000. 1198 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Peces). 5 records from Heteragrion lencionii (Odonata: Heteragrionidae) sp. nov. from Serra de Itabaiana National Park, Northeastern Brazil. 14 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 8 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 201 records from Schanzenanlage Bergham. 74 records from Reptiles presentes en la colección herpetológica SINCHI de la expedición al Río Apaporis - Proyecto Colombia BIO. 24 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 22 records from Contributions to the study of the grasshopper (Orthoptera: Acrididae Gomphocerinae) courtship songs from Kazakhstan and adjacent territories. 170 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 70 records from The interstitial subsoil fauna of the lower beach level at Sarso Beach, Red Sea (Table 4). 160 records from AVJNF: Søholt Storskov, amphibian survey. 580 records from Free-living plathelminthes of marine habitats near Wimereux (1990-1991). 549 records from Données du Geckos vert des Hauts (Phesulma borbonica) du Parc national de La Réunion. 1 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 25 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 14 records from New host-plants records of Afrotropical Gelechiidae (Lepidoptera), with description of three new species. 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 5 records from Satellite Tracking of Hawksbill Turtle in West Sumbawa, Indonesia (aggregated per 1-degree cell). 15 records from Monitoreo de Murciélagos en la Etapa de Ejecución de las Obras de Ampliación del EPF Floreña, Yopal, Casanare. 5 records from The InBIO Barcoding Initiative Database: DNA Barcoding reveals sexual dimorphism in Isotrias penedana Trematerra, 2013 (Lepidoptera: Tortricidae, Chlidanotinae). 6 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 85 records from Hidden gems in museum cabinets: new species and new distributional records of Scolytodes (Coleoptera: Scolytinae). 135 records from Inventaire faunistique de l'ENS des Parc des berges de Seine. 3 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 2809 records from Benthos Chirnov Basin 1986 and 2002. 5412 records from Soil invertebrates occurrences in European North-East of Russia. 684301 records from Queensland Museum provider for OZCAM. 6 records from A taxonomic reappraisal of the Smooth Slug Snake Asthenodipsas laevis (Boie, 1827) (Squamata: Pareidae) in Borneo with the description of two new species. 6387 records from Données naturalistes de Monsieur LAFAGE Denis. 1071 records from IPAE egg clutches collection (Aves). 5 records from On the genera Ptiloneura Enderlein, Loneura Navás, and Loneuroides García Aldrete (Psocodea: ‘ Psocoptera’: Ptiloneuridae). 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 1 records from Molche in Ruschwedel. 133 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 14 records from A review of the bats (Chiroptera) of the Republic of Congo, including eight species new to the country. 9115 records from Données d'observations d'orthoptères en Auvergne, d'Emmanuel Boitier, de 1998 à 2015.. 6 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 26 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 127 records from Freshwater crustaceans in Antarctic and sub-Antarctic lakes. 701 records from Données naturalistes d'Arnaud LE NEVÉ. 9 records from A review of Solierella Spinola, 1851 (Hymenoptera, Crabronidae) from Iran with description of four new species. 4 records from Ollieopteryx, a new genus of caddisflies from Madagascar (Trichoptera Dipseudopsidae). 3 records from Analyses of the recent components of sediment core PS1219-1. 94 records from Happywhale - Leopard seal in South Atlantic Ocean. 717 records from Redland City Council Citizen Science Portal. 1 records from New Zealand forest-dwelling skinks of the Oligosoma oliveri (McCann) species-complex (Reptilia: Scincidae): reinstatement of O. pachysomaticum (Robb) and an assessment of historical distribution ranges. 9 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 180 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 253 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 6 records from Pollen record of profile 3TZ. 444 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 2 records from Happywhale - Southern Bottlenose Whale in Southern Ocean. 54 records from "Ahrschleife bei Altenahr". 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 408255 records from South Australian Museum Australia provider for OZCAM. 2 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 11 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 47 records from Unter hellen Zinnen und finsteren Grotten. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 10167 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 10 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 2269 records from UNCW Marine Mammal Aerial Surveys 2006-2007. 97 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 2 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 278 records from Gomex Sperm Whale Survey 2000. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 2350 records from Modernisation des ZNIEFF du PnrL. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 12 records from Occurrence of mammalia relicts at site Niederlehme. 155 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 38 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 1264 records from Grand Voyeux - Suivis scientifiques. 86 records from UWIZM Cnidarians. 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 150 records from Ningaloo Outlook Whale Shark tracking (aggregated per 1-degree cell). 299 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 32399 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 80 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 174618 records from Tasmanian Museum and Art Gallery provider for OZCAM. 14329 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 938 records from TTRS Mammals. 123 records from Occurrence of mammalia relicts at site Veternica. 6 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 6 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 1 records from Genetic and morphological evidence for cryptic species in Macrobrachium australe and resurrection of M. ustulatum (Crustacea, Palaemonidae). 45 records from Brown bear monitoring data from Deosai National Park. 1547 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 12 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 26 records from Synthèse de la Répartition des populations de mouflon corse en 2011 (réseau Ongulés sauvages ONCFS-FNC-FDC). 93421 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1 records from Occurrence of mammalia relicts at site High Furlong. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 53 records from Occurrence of mammalia relicts at site la Grotte des Eglises. 31 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 90 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 1254 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) UiT Tromsø Museum. 29 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 1 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 33 records from Faunal assemblage of sediment core TR149-32. 787 records from Programme ACT : Répartition Pie bavarde 2009 - 2013 Coordonnées GPS Lambert 93. 62 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 82 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 3 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 1913 records from Registros Primates Neotropicales Convocatoria APC. 13 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 5 records from Pollen record of profile 3TZ2. 2 records from New Descriptions Of North American Taenionema Larvae (Plecoptera: Taeniopterygidae). 31 records from Schulgelände Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 1 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 35 records from Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Glöer, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 12 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 3 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 8 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 70 records from Swedish Malaise Trap Project (SMTP) - Odonata. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 83 records from Birdrace-Die_Vogelscheuchen-Herford. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 26 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 373 records from Otter survey of Ireland 2004 & 2005. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 1292 records from Happywhale - Gray Whale in North Pacific Ocean. 129891 records from Suivi Temporel des Rhopalocères de France (STERF). 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 17 records from Cellaria (Bryozoa, Cheilostomata) from the deep: new species from the southern Zealandian region. 15 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 23 records from Australian Museum Ichthyology - 2012 Inscription Point. 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 10 records from Landwehrbach. 940 records from SeaTurtle surveys on Braamspunt by Green Heritage Fund of Suriname. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 38 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 9632 records from CSIRO, fish surveys by the Soela, 1980s. 323 records from Données de VINCENT Alexis (SAPROX). 1162 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 3 records from A new species-group with new species of the genus Lasioseius (Acari: Mesostigmata: Blattisociidae) associated with Neotropical hispine beetles in furled leaves ofHeliconia. 1171 records from Glasgow Museums BRC: Chrysomelidae. 4 records from New Species And Records Of Anacroneuria (Plecoptera: Perlidae) From Ecuador And Paraguay. 51 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 2 records from The deep-water Calappidae, Matutidae and Leucosiidae of the Solomon Islands, with a description of a new species of Euclosia Galil, 2003 (Crustacea, Decapoda, Brachyura). 8423 records from University Of Pretoria: Lacewing Database Project (1911-2015). 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 28 records from Bryde’s whales off eastern Venezuela - Vessel 1978-1979. 3277 records from USAC Mammals Collection. 130 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 2 records from Happywhale - Dusky Dolphin in South Pacific Ocean. 1 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 3350 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 106 records from Occurrence of mammalia relicts at site Geißenklösterle. 23 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 74 records from Steinbruch Mainz-Weisenau, 3. Jahr. 972 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 25 records from Pollen profile V and Ausfluss at Krumbach, Germany. 547 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 1 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 229 records from Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations. 186805 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 355 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (75° N section). 5 records from Two new species of Guyruita Guadanucci et al., 2007 (Araneae, Theraphosidae) from Brazil. 3 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 35 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil. 1 records from A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific. 718 records from Bird species occurrences recorded from selected sites in mid Tana River Basin, Kenya. 143568 records from Movement patterns of Peruvian Boobies off Isla Lobos de Tierra 2006. 66 records from Wildlife Sightings in the City of Logan. 1 records from Temporal dynamics of bacterioplankton community in response to excessive nitrate loading in the oligotrophic coastal water. 368 records from Données du naturaliste PROVOST romain provenant de la base de donnée du SINP Île-de-France CETTIA. 16253 records from Birds Specimens. 56 records from Schulgelände Kranich-Gymnasium (Salzgitter). 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 592 records from Caracterización de Fauna del Banco de Hábitat del Bosque Seco Tropical Antioquia de Terrasos. 453 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : données espèces non cibles piégées. 33 records from Fliegenhaupt Marksuhl. 66 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 18449 records from DMNS Mammal Collection (Arctos). 98 records from Occurrence of mammalia relicts at site Rejtek 1. 1 records from A new species of the genus Pachytriton (Caudata: Salamandridae) from Hunan and Guangxi, southeastern China. 1 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 776 records from Relative abundance of adult opstracoda shells of surface sediment samples from the Persian Gulf (Table 1b). 81 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 66 records from Tortugas Marinas del Golfo de California (aggregated per 1-degree cell). 64 records from Bats of northeastern Vietnam. 785 records from Colección de Mamíferos Marinos del Centro Nacional Patagónico. 13 records from A New Species Of Capnia Pictet, 1841 (Plecoptera: Capniidae) From Kyushu, Japan, With Description Of Male Drumming Signals. 214 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 4 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 1 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 1688 records from BenthosChukchiFN762_1976_Falk5. 1560 records from Pacific turtle tracks: Turtle-Safe Seas Project. 43 records from Macrofauna abundance in surface sediment sampled during cruise DI237. 117 records from Programme de valorisation des zones humides chassées - volet Amphibiens. 5 records from New data on jumping spiders of Iran, with a new species of Salticus (Araneae: Salticidae). 1870 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 33 records from New and little-known sun-moth species from Australia (Lepidoptera, Castniidae). 42 records from Fig. 4. Pollen record of profile SAO1 (Analyst: J. Hahne). 1 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 89 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 21999 records from Port Phillip Bay Environmental Study Data 1992-1996 - benthic records. 63 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 2 records from A new crab-associated amphipod of the genus Isaeopsis Barnard, 1916 (Amphipoda Senticaudata: Ischyroceridae) from southern Chile. 3238 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 60 records from Knechtweide (Kohlfurth). 11 records from Benthic macrofauna abundance of sediment core 12930-073. 90 records from MCP-Mamiferos - Coleção de Mamíferos. 96 records from The Echinoderm Fauna of the Azores (NE Atlantic Ocean). 358 records from Données du Syndicat de la Vallée de l'Orge Aval (SIVOA). 89 records from Meniscus Midges (Dixidae) of Ireland. 1017 records from Programme ACT : Répartition Merle noir 2001 - 2005 Coordonnées GPS Lambert 93. 7 records from Description of a new species of Glassella Campos & Wicksten, 1997 from a coastal lagoon, SE Gulf of California (Crustacea, Decapoda, Pinnotheridae). 509 records from Occurrence database of native plants and animals of south-central Chile. 170 records from Alien Species in Poland - Animals. 23 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 13 records from Three new species and three new records of the genus Bamboosiella from China (Thysanoptera: Phlaeothripidae). 100048 records from Swiss National Bat Databank: Regional Coordination Western Switzerland (CCO). 4 records from Cryptic diversity across the Trans-Mexican Volcanic Belt of Mexico in the montane bunchgrass lizard Sceloporus subniger (Squamata: Phrynosomatidae). 92 records from Natura 2000 Parc naturel régional de Lorraine. 144282 records from Données de l'AFB acquises selon le protocole de pêche complète à un ou plusieurs passages. 2 records from Nothobranchius nikiforovi, a new species of seasonal killifish from the lower Matandu drainage in south-eastern coastal Tanzania (Cyprinodontiformes Nothobranchiidae). 1343 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 25 records from Sierraperla Jewett, 1954 (Plecoptera: Peltoperlidae), Distribution, Egg Morphology And Description Of A New Species. 3 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 973 records from Zambian Bat Collections Worldwide. 14 records from A new freshwater shrimp species of the genus Palaemon Weber, 1795 (Decapoda: Caridea: Palaemonidae) from northeastern Japan. 1 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 143 records from BIRDRACE Punkbirder Helgoland. 277 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 36 records from Lynx 1992 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 3 records from Campydoroides manautei gen. et sp. nov. from New Caledonia and a reappraisal of the suborder Campydorina (Nematoda). 4 records from A new species of the greeneye genus Chlorophthalmus (Teleostei: Chlorophthalmidae) from the central North Pacific. 243 records from Fish species occurrences from selected near shore and riverine habitats in Lake Edward (2019). 6 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 264 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 2 records from More cautionary tales: family, generic and species synonymies of recently published taxa of ghost and mud shrimps (Decapoda: Axiidea and Gebiidea). 24 records from Review of the Taiwanese Laccobius Erichson, 1837 (Coleoptera: Hydrophilidae) with description of a new species. 2271 records from Helmintos parásitos de peces del sureste de México. 383 records from Inventario de Peces del SFF Isla Malpelo, Proyecto Colombia Bio. 28 records from Naturpark Kottenforst-Ville 15.6.09. 2 records from Cnemaspis rajakarunai sp. nov., a rock dwelling day-gecko (Sauria: Gekkonidae: Cnemaspis) from Salgala, an unprotected lowland rainforest in Sri Lanka. 18 records from Catch related distribution of Appendicularia at station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 8). 1 records from Rhopalomenia glandulosa spec. nov., and the restoration of Entonomenia Leloup (Mollusca: Solenogastres). 1 records from Microbial ecology of bacteiral community in sediment from adjacent waters of Rushan Bay. 3 records from The larva of Lestes alfonsoi Gonzalez & Novelo (Zygoptera: Lestidae). 2 records from Studies on Ramulus ussurianus (Bey-Bienko, 1960) (Phasmida: Phasmatidae). 2 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 1 records from seawater metagenome Metagenome. 4333 records from Heliconiine Butterfly Collection Records from University of Cambridge. 27 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 2436 records from Diet results from Adelie penguins at Bechervaise Island and Whitney Point, 2012/13. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 5 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 1468 records from Colección Regional de Equinodermos de la Peninsula de Yucatan. 6 records from (Table 1) Nesting characteristics of greater snow geese (Chen caerulescens atlanticus) on Bylot Island between 1995-2005. 943 records from Programme ACT : Répartition Tourterelle turque 2012 - 2016 Coordonnées GPS Lambert 93. 355 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 4 records from Determinación de la clase Reptilia presente en el corregimiento de Juanchaco, Valle del Cauca, Colombia para el mes de Septiembre de 2017. 508 records from Northern elephant seals post-molting 2017 (aggregated per 1-degree cell). 56 records from Tejidos colectados en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 79 records from Birdrace-Bielefinken-Bielefeld. 48 records from Müritz-Nationalpark. 121 records from Range table from ostracoda in ODP Hole 143-866B. 8540 records from Kenai National Wildlife Refuge, Alaska (KNWR) Insect specimens (Arctos). 4054 records from Fish specimens of Toyama Science Museum. 14 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 4653 records from Colección Limnológica Universidad de Antioquia. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 378 records from Rock ptarmigan (Lagopus muta) radio telemetry in Lierne, Norway. 92 records from Wald am Schloss Wittgenstein Bad Laasphe. 503 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 215 records from Shoreline fish distribution in Italian lakes assessed by electrofishing. 8 records from Four new species of Diptilomiopinae from China (Acari: Eriophyoidea: Diptilomiopidae). 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 19 records from Schulgelände SGD/Viersen. 1533 records from Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 69 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 10692 records from TOPP Summary of SSM-derived Telemetry. 1 records from A new species and southernmost record of Cestrus Townes (Hymenoptera Ichneumonidae, Cryptinae). 53 records from Leopard and Weddell seal program 1999/2002. 3608 records from Données naturalistes de Ségolène FAUSTEN. 4 records from New records of phytoseiid mites from Mauritius Island (Acari: Mesostigmata. 2 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 9384 records from MZL Invertebrate Collections. 4 records from Range table from benthic foraminifers in ODP Hole 181-1119C. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 14 records from Two New Species Of Dictyogenus Klapálek, 1904 (Plecoptera: Perlodidae) From The Jura Mountains Of France And Switzerland, And From The French Vercors And Chartreuse Massifs. 1 records from New look on the geographical variation in Rhinolophus clivosus with description of a new horseshoe bat species from Cyrenaica, Libya. 4 records from Four new species of Xiphocentron Brauer, 1870 (Trichoptera: Xiphocentronidae) from the Atlantic Forest, southeastern Brazil. 13940 records from Collection of Coleoptera. 37 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 352 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 11732 records from Invertebrates of the river Tana Basin in Kenya available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section. 2 records from Redescription of Stilobezzia (Stilobezzia) albicoxa Lane & Forattini, 1956 with new synonymy (Diptera: Ceratopogonidae). 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 11 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 485 records from Rothschild Giraffe occurrence records observed at Mwea National Reserve in Central part of Kenya. 37 records from Revision of New World Cosmorrhyncha Meyrick, 1913 (Lepidoptera: Tortricidae: Olethreutinae), with descriptions of five new species. 160 records from Acquario di Genova, Delfini Metropolitani Project, cetacean sightings 2001-2009. 2 records from Unveiling the morphology of the Oriental rare monotypic ant genus Opamyrma YAMANE, BUI & EGUCHI, 2008 (Hymenoptera: Formicidae: Leptanillinae) and its evolutionary implications, with first descriptions of the male, larva, tentorium, and sting apparatus. 8956 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 642 records from Ensemble des données Rhopalocères. 14236 records from Tachinid Recording Scheme - Tachinid fly records verified via iRecord. 3529 records from A dataset from bottom trawl survey around Taiwan. 3 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 6651 records from Données naturalistes de LUPOLI Roland. 68 records from Données du/de la naturaliste JOSSERAND oriane provenant de la base de donnée du SINP Île-de-France CETTIA. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 1129 records from Catopsilia butterfly specimens at Museum Zoologi Bogor, Indonesia. 658 records from Inventarios de la biodiversidad en el piedemonte subandino de Yopal. 2 records from Two new species of stargazers of the genus Uranoscopus (Teleostei: Uranoscopidae) from the western Pacific Ocean. 86 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 336 records from Données naturalistes de François BRETON. 16 records from NC Aquariums Cold Stunned Sea Turtle Monitoring (aggregated per 1-degree cell). 3 records from First record of the myrmicine ant genus Syllophopsis Santschi, 1915 (Hymenoptera Formicidae) from India with description of a new species. 8 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 9120 records from Coral Reef Evaluation and Monitoring Project Florida Keys 1998. 20 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2004. 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 1 records from A mid-Cretaceous female scale insect (Hemiptera: Sternorrhyncha: Coccomorpha) in Burmese amber. 5 records from Copepoda (Siphonostomatoida: Dirivultidae) from Hydrothermal Vent Fields on the Central Indian Ridge, Indian Ocean. 24430 records from EDP Foz Tua: Terrestrial Birds, Winter (point counts) - Ecological Monitoring Program [2011-2017]. 67 records from Post-nesting migration of loggerhead turtles around Japan 2005 (aggregated per 1-degree cell). 12 records from Lepidoptera specimen database of Japan. 2499 records from Leicestershire and Rutland Reptile Records to 2011. 5640 records from Solenosmilia matrix annotations and VME habitat identification in video from voyage IN2018_V06, Australia (2018). 3664 records from Collection Vermes - ZMB. 130 records from BIRDRACE - The famous Grouse feat. The James. 63 records from Distribution of meiofauna in surface sediments of the Iberian deep sea basin (Table 3). 7 records from Parasitoides de Cochinilla. 1 records from Mumetopia interfeles sp. nov., a new species of Anthomyzidae (Diptera) occurring en masse in an urban grassy habitat in Chile: its taxonomy, phylogeny and biology. 2 records from Baetis pentaphyllus sp. nov., a new species of mayfly (Ephemeroptera: Baetidae) from the Russian Far East. 294 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 2 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 372 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 2 records from Taxonomic review of the genus Compsiluroides Mesnil (Diptera: Tachinidae), with the description of a new species. 1 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 6 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 21 records from New genera for species of Jassa Leach (Crustacea: Amphipoda) and their relationship to a revised Ischyrocerini. 165 records from Coarse fraction analysis and texture of biogenous sands from Josephine Seamount surface samples (Table 2). 74 records from Anfibiofauna asociada a la quebrada Giginia, corregimiento de Doña Josefa, Municipio del Atrato - Chocó, 2019. 29 records from Occurrence of mammalia relicts at site Goyet Cave 3. 37 records from FBIP: scallop population genetics. 18 records from Schulgarten der Gesamtschule Am Heidberg. 2091 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 1245 records from Données du/de la naturaliste Lantz André provenant de la base de donnée du SINP Île-de-France CETTIA. 12 records from New species of Condylostylus Bigot (Diptera: Dolichopodidae) from Comoros Madagascar, Tanzania and South Africa, with key to Afrotropical species. 167 records from Read between the lineata: A revision of the tattooed wasps, Zagrammosoma Ashmead (Hymenoptera: Eulophidae), with descriptions of eleven new species. 2 records from The genus Synergus Hartig (Hymenoptera: Cynipidae: Synergini) in the New World: a complete taxonomic revision with a key to species. 153 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE1. 12 records from (Tab. 6) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 41-370, Deep Basin West off Morocco. 23 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 4 records from Society Islands beach bum black flies (Diptera: Simuliidae). 2725 records from Computarización de material complementario en la Colección Regional de Invertebrados del Pacífico mexicano, Instituto de Ciencias del Mar y Limnología, Unidad Académica Mazatlán, UNAM. 58 records from Données naturalistes de BONCHE Jérôme. 304 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 79758 records from natagora-earlybirds. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 4 records from Happywhale - Spinner Dolphin in North Atlantic Ocean. 6 records from Biodiversity of spider mites (Acari: Tetranychidae) in Serbia: a review, new records and key to all known species. 9 records from Character state variation within Dendrothrips (Thysanoptera: Thripidae) with a revision of the species from China. 6862 records from Hormigas del Museo de Entomología de la Universidad del Valle. 29 records from Reptiles Specimens of Akita Prefectural Museum. 338 records from UWIZM Snakes. 8 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 43 records from Tejidos colectados en el piedemonte llanero, Boyacá - Proyecto Boyacá BIO. 145 records from Biodiversity survey of Rugezi wetland, Year 2013. 4 records from Crustáceos del municipio Santa Bárbara, Santander - Proyecto Santander BIO. 43736 records from NOAA coral reef monitoring benthic data from sites across Micronesia from 2009-09-29 to 2015-09-25. 121 records from Etude écologique du Parc des Lilas (94). 12 records from Données bibliographiques ASFRA. 69 records from PRESENCIA DE VISÓN AMERICANO EN TIERRA DEL FUEGO, MAGALLANES, CHILE. 22 records from Microzooplankton abundance and biomass at station TT043_27-1. 1 records from Brachiopods Specimens of Akita Prefectural Museum. 34 records from Database of European river lamprey (Lampetra fluviatilis (Linnaeus, 1758)) actual samples deposited in the A.N. Severtsov Institute of Ecology and Evolution. 1027 records from Fish and crustacean community in the Western Scheldt (Doel nuclear power station) during winter season 1991-1992. 301 records from Northern elephant seals post-breeding 2015 (aggregated per 1-degree cell). 16 records from Notes on the Dianous aereus complex with description of a new species (Coleoptera, Staphylinidae). 1 records from A new Aceria species (Acari: Prostigmata: Eriophyoidea) from Minuartia frutescens (Caryophyllaceae) in Hungary. 6 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 2340 records from Butterflies of Singapore and Peninsular Malaysia (Nymphalidae). 43 records from Renaturierung Werse (Innenbereich Beckum). 23 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1a. 254 records from Atlantic Forestry Centre Insect Reference Collection. 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 3 records from A new species of Flavoperla Chu, 1929 (Plecoptera: Perlidae) from Guangxi Zhuang Autonomous Region of southern China. 11452 records from Dragonfly (Odonata) species records up to 1997 held by Leicestershire Environmental Resources Centre. 9 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 2807 records from Coleção de Ictiologia ABAM do Campus Sinop da UFMT. 2 records from Two new species of Spider Wasps (Hymenoptera, Pompilidae), Ctenagenia pagliano from Lebanon and Evagetes liane from Canary Islands. 113 records from South Lanarkshire peatland records 2013. 11 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 529 records from NEFSC Mid-Atlantic Marine Mammal Abundance Survey 2004. 83 records from Données du/de la naturaliste GAUTHIER Nicolas provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from First report of the old world genus Pelecystola in North America, with description of a new species (Lepidoptera, Tineidae). 682 records from Transferts SI Faune - Données naturalistes opportunistes de Cedric DEVILLEGER. 1653 records from Derbyshire Casual LEPIDOPTERA records - Casual records collated by Derby Museum.. 2 records from Two new species of the genus Daptonema Cobb, 1920 (Nematoda: Xyalidae) found in an intertidal seagrass bed on the coast of the Andaman Sea, Thailand, with reference to the taxonomic status of the genus Trichotheristus Wieser, 1956. 30 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 50 records from Institut Mediterrani d'Estudis Avançats (CSIC-UIB): IMEDEA-OTO. 1 records from A new, peculiar genus of Cossoninae (Coleoptera, Curculionidae) from Oman with description of a new species, larva and notes on biology. 15251 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 30 records from New distributional records of Staphylinina in Taiwan, including a new species of Miobdelus Sharp (Coleoptera: Staphylinidae: Staphylininae: Staphylinini). 3 records from A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia). 277 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 6 records from Pauximyia, a new genus of Odiniidae (Diptera: Acalyptratae) with description of two new species from Brazil. 31 records from Lepidurus arcticus survey Northeast Greenland 2013. 1 records from A Revision of Philander (Marsupialia: Didelphidae), Part 2: Phylogenetic Relationships and Morphological Diagnosis of P. nigratus Thomas, 1923. 48 records from VSN-Wiese. 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 2 records from A new species of Liriomyza Mik (Diptera, Agromyzidae) on okra in Brazil. 2 records from A new genus and species of anophthalmous Otiorhynchini from Greece, with a new synonymy and new combinations (Coleoptera: Curculionidae, Entiminae). 25 records from Fortalecimiento de la efectividad del manejo y la resiliencia de las áreas naturales protegidas para proteger la biodiversidad amenazada por el cambio climático. 904 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 67 records from Relative abundance of ostracods in sediment core Sv09. 4840 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 104 records from Ecological study of the plankton in the port of Ostend in 1965. 30 records from Révision du genre Danuriella Westwood, 1889 (Mantodea). 93036 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 3 records from A new species of Neobathyclupea from the northern Indian Ocean with comments on N. malayana (Teleostei, Perciformes, Bathyclupeidae). 8 records from Lepidepecreoides stoddartae sp. nov. from the Falkland Islands (Amphipoda: Tryphosidae). 1653 records from The Belgica 121 expedition to the Western Antarctic Peninsula: a high resolution biodiversity census. 32 records from Happywhale - Killer Whale in Arctic Ocean. 1 records from Two new species of Plutomurus Yosii (Collembola, Tomoceridae) from the Caucasus. 3 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 10 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 122 records from FFH-Gebiet Klosterwasser/Burkau. 7 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 255 records from Données naturalistes de Hubert GUIMIER. 2 records from Revision of the genus Systellapha Enderlein (Micropezidae, Taeniapterinae). 1796 records from Données de la collection Rousset -1947-2013. 1807 records from Données naturalistes de Hervé BOUYON. 10 records from Ten new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Southeast Asia. 874 records from Programme ACT : Répartition Grive musicienne 2004 - 2008 Coordonnées GPS Lambert 93. 254 records from Thistle Heads and Ermerged Insects. 134 records from Lynx 2005 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 87 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 1 records from A New Free-living Marine Nematode Species of the Genus Graphonema (Nematoda: Chromadorida: Chromadoridae) from Antarctica. 363 records from Colección Herpetológica de la Patagonia. 3128 records from Données DREAL Centre-Val de Loire - Faune - 2018. 1 records from Redescriptions of ten chigger mite species (Acariformes: Trombiculidae) from Vietnam. 54670 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 2 records from Comparative metagenome analysis of normal and arsenic contaminated soils from ballia district, Uttar Pradesh, India. 33 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 9054 records from Highland bird data 2002 - 2003 - non-breeding records. 7775 records from 1994-2020 Capercaillie Cold Searches Data, Scotland. 7 records from Revision of the genus Cobbionema Filipjev, 1922 (Nematoda, Chromadorida, Selachinematidae). 1 records from Uncultured Environmental Isolate Targeted loci environmental. 3463 records from RNF - Données du Parc Naturel Régional du Vercors. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 206 records from Registros de geckos en Colombia asociado al proyecto: The small world of Lepidoblepharis. 3079 records from Insectes Hyménoptères Scollidés de France. 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 2279 records from The hoverfly collection (Diptera, Syrphidae) of the International Institute of Tropical Agriculture (IITA) at Calavi (Benin). 3978 records from Weddell Sea macrozoobenthos EASIZ I. 916 records from IOW Natural History & Archaeological Society Marine Records. 4 records from A new South American species of Banasa Stål (Hemiptera: Heteroptera: Pentatomidae: Pentatominae): from egg to adult. 13 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 5398 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 71 records from Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010. 2087 records from Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 2 records from Seawater metagenome Targeted loci environmental. 9 records from Occurrence of mammalia relicts at site Climauti II. 80 records from Waldi-Weiher. 292 records from Gewann Krampf (Heilbronn). 4 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 43 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 25 records from Données de NICOLAS Vincent (SAPROX). 15 records from Benthic macrofauna abundance of sediment core 13201-002. 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 493 records from Fauna and population of oribatid mites (Acari, Oribatida) in the vicinity of Kosogorsky metal works (Tula Region, Russia). 1013 records from Circumpolar Seabird Monitoring Plan. 21 records from Pollen profile from Muscotah Marsh B. 29 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 14 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 49 records from Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 7 records from A New Species Of Perlesta (Plecoptera: Perlidae) From North Carolina With Additional Records For North Carolina And Virginia. 296 records from HRC SCC Aerial-Based Monitoring Survey February 2010. 1850 records from Trondheim urban biodyversity survey. 94 records from Données du/de la naturaliste LUSTRAT Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 89 records from Taxonomy and molecular phylogeny of the Platystictidae of Sri Lanka (Insecta: Odonata). 58 records from Swedish Malaise Trap Project (SMTP) - Banchini. 186 records from (Table II) Abundance of epibenthic phyla and classes during RSS James Clark Ross cruise JR144. 19 records from New species of Hercostomus Loew, 1857 from Afrotropics (Diptera: Dolichopodidae) and key to Afrotropical fauna. 660 records from Peces pelágicos de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 12 records from A revision of the spider genus Anemesia (Araneae, Cyrtaucheniidae). 11034 records from Oregon Bee Atlas Survey Data: 2018. 8792 records from UAM Fish Collection (Arctos). 200 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 8808 records from Survey of bumblebees in central Alberta - 2018. 70 records from Isotope tracer experiment: meiofauna counts. 2 records from New data on the taxonomy and distribution of Philippine Ochodaeidae and description of a new species from Central Visayas (Coleoptera: Scarabaeoidea). 30 records from Bird Specimens of The Cattle Museum. 557 records from Corn bunting breeding distribution in Scotland. 1210 records from NEFSC Marine Mammal Abundance Cruise 2004 Passive Acoustic Monitoring - Rainbow Click Detections. 919 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 71 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 4 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 2 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 66 records from Selztal bei Friesenheim. 2 records from Foraging Greens and Hawksbill Bare Sand Island (aggregated per 1-degree cell). 4 records from New records and checklist of Chilocorini (Coleoptera: Coccinellidae) from China. 41 records from Hydroptilidae (Trichoptera) of Angola, a new genus, seven new species, and five new records. 18 records from Microzooplankton abundance and biomass at station TT045_19-3. 1458 records from UCM Mammal Collection (Arctos). 43 records from (Figure 4) Distribution chart of benthic foraminifers in ODP Site 126-791. 2 records from Natural History Museum, Vienna - Herbarium W. 7 records from Quadrige. 1 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 9 records from A new species of Proterhinus Sharp, 1878 (Coleoptera: Curculionoidea: Belidae) from Miti‘aro, Cook Islands, South Pacific. 869 records from Programme ACT : Répartition Grive musicienne 2005 - 2009 Coordonnées GPS Lambert 93. 65 records from Biologia reprodutiva e dieta de Amerotyphlops brongersmianus (Vanzolini, 1976) da Restinga de Jurubatiba, Rio de Janeiro, Brasil (Serpentes: Typhlopidae). 1942 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Verdon_2017_12_18. 30 records from Feral Pigs - Sightings and Cull records - 2014-2015. 86 records from Occurrence of mammalia relicts at site Bocksteinschmiede. 1 records from On the systematic status of Calliophis macclellandi nigriventer Wall, 1908 (Reptilia: Serpentes: Elapidae). 29 records from Mesostigmatic mites (Acari: Mesostigmata) of Saudi Arabia (excluding Phytoseioidea), new records and a key to the known species. 1 records from Description of the larva of Orthemis ferruginea (Fabricius, 1775) (Odonata: Libellulidae). 52 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/574-1. 859 records from Floral visits on plants, InsectScale 2008. 2510 records from Kenya Wildlife Service, Laikipia Samburu Aerial Census, 2012. 63 records from Cetacean coordinated transborder monitoring using ferries as platforms of observation off Tunisia 2013-2014 - Atutax. 18 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 3 records from Two new species of tribe Agalliini (Hemiptera: Cicadellidae: Megophthalminae) with note on intraspecific variations. 43 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 2 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 29 records from Données espèces - Expertise IPE 70. 12 records from Two new genera and three new subterranean species of Hydrobiidae (Caenogastropoda: Truncatelloidea) from Tunisia. 944 records from NOAA coral reef monitoring invertebrate data from sites across Micronesia from 2009-09-29 to 2015-09-25. 4570 records from Biogeography of near-shore reef fishes in northern New Zealand. 20 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 3 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 87 records from Steinbruch Mainz-Weisenau, 2. Jahr. 11 records from The InBIO Barcoding Initiative Database: A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann, 1870 (Lepidoptera, Depressariidae). 1 records from Happywhale - North Atlantic Right Whale in North Atlantic Ocean. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 20 records from Description of lithologic section units of IODP Hole 325-M0033A. 2172 records from ConDidact Citizen Science Surveys - Snails 2006. 21 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 28 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 88 records from Deponie Klausdorf. 30 records from Schulgelände (Wetter). 712 records from Earthworm Research Group (UCLan) Earthworm Records (UK). 16 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 2 records from A new species of Polyamia DeLong (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) representing the first record of the genus from South America. 247 records from DUML vessel-based photo-id and biopsy surveys for proposed JAX USWTR site 2012-2015. 2387 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 14391 records from Enquête Lucane. 425 records from Erlengraben/Lipp-Tal (Östringen). 56582 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 1986 records from Observations de Coléoptères saproxyliques de Frédéric LACOSTE. 2 records from A new species of the genus Diogenes Dana, 1851 (Crustacea: Decapoda: Anomura: Diogenidae) from Gujarat, northwestern India. 2 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 391 records from Expédition Karubenthos 2012 : inventaire des Echinodermes de la Guadeloupe. 1484 records from Population research on small rodents (Rodentia) and screws (Soridae) in Steinkjer Municipality – Norway; 2018 - 2019 based on systematic catches with ordinary mouse traps in traplines. 1 records from New species of Neohybos Ale-Rocha & Carvalho (Diptera, Hybotidae, Hybotinae) from South America. 2432 records from BioGIS - Reptiles - HUJ collections. 1 records from Analyses of the recent components of sediment core PS1222-1. 271 records from Flora Atlas N.T.. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 5154 records from Fishes in the Argentine Sea from 1967 to the present time. 3 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 46 records from New species of Helicopsyche von Siebold 1856 (Trichoptera: Helicopsychidae) from Brazil, including the redescription of Helicopsyche (Feropsyche) planorboides Machado 1957. 71 records from A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea). 14 records from Three new species of the subgenus Jaynesia Allen, 1969 of the genus Tiphia Fabricius, 1775 (Hymenoptera: Tiphiidae: Tiphiinae) from China, with a key to all known species. 1 records from A new species of Pseudocrenilabrus (Perciformes: Cichlidae) from Lake Mweru in the Upper Congo River System. 72474 records from CAS Invertebrate Zoology (IZ). 19 records from Ophioderma hendleri sp. nov. (Echinodermata: Ophiuroidea: Ophiodermatidae) and its congeners from the Eastern Pacific. 1 records from water Raw sequence reads. 41 records from Etude d'impact projet d’ouverture de carrière à Vaudoy-en-Brie. 55 records from Macroinvertebrados bentónicos de playas de arena (Monte Hermoso-Pehuen Có, Buenos Aires, Argentina). 6 records from Leafhopper tribe Coelidiini (Hemiptera: Cicadellidae: Coelidiinae) of the Indian subcontinent. 15 records from See lilies of the genus Bathycrinus (Echinodermata, Crinoidea: Bathycrinidae) from the North-West Pacific hadal trenches. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 810 records from Taxonomía y distribución de los filópodos (Crustacea: Branchiopoda, Anostraca, Notostraca, Spinicaudata y Laevicaudata) de México. 102 records from Annotated catalog of the type specimens deposited at the fish collection of the “ Universidade Estadual Paulista, Câmpus de São José do Rio Preto ”, São Paulo, Brazil (DZSJRP). 119 records from Suivi des leucorrines sur le site du Marais du Plata. 4 records from Laminatubus (Serpulidae, Annelida) from eastern Pacific hydrothermal vents and methane seeps, with description of two new species. 515 records from Kenai National Wildlife Refuge, Alaska (KNWR) Bird observations (Arctos). 8848 records from EDP Baixo Sabor: Birds - Construction and Reservoir Filling Phases - Vilariça Stream (MC1) [2013-2014]. 146 records from Abundance of birds in the Lena Delta Region. 7 records from Descriptions Of The Adult Male And Female Genitalia Of The Genus Osobenus Ricker (Plecoptera: Perlodidae). 31 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 433 records from Synthèse de la Répartition des populations de chamois en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC). 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 35 records from Ortsrand Zandershagen. 69 records from artsprosjektet_48-13_monomyx. 2 records from Happywhale - Southern Right Whale Dolphin in South Atlantic Ocean. 1 records from Crickets of the genus Gryllus in the United States (Orthoptera: Gryllidae: Gryllinae). 4 records from The Odonata of Sulawesi and adjacent islands. Part 8. Revision of the genus Rhinocypha Rambur, 1842 (Chlorocyphidae). 1 records from Occurrence of mammalia relicts at site Ballybetagh. 505 records from National Frog Survey of Ireland 2010/2011. 585 records from Chronicle of Nature - Phenology of Insects of State Nature Reserve Kivach. 1 records from marine sediment metagenome Raw sequence reads. 130 records from Dubai Turtle Rehabilitation Project (aggregated per 1-degree cell). 20191 records from Seabirds in Norway - Estimated population sizes. 12156 records from WADFW PSAMP S1992. 26 records from Occurrence of mammalia relicts at site Rusenschloß. 12 records from Kenai National Wildlife Refuge, Alaska (KNWR) Fish observations (Arctos). 9 records from Benthic macrofauna abundance of sediment core 12930-048. 442 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 154 records from HRC USWEX Aerial-based Shoreline Surveys February and March 2011. 5360 records from Colección Ornitológica de la Universidad del Valle. 794 records from USWTR JAX Aerial Survey -Right side- 2009-2010. 4 records from On the Italian species of Drusilla L, 1819, with a note on D. taygetana A (Coleoptera: Staphylinidae, Aleocharinae). 8 records from Revision of the South American species of Austrothaumalea Tonnoir (Diptera Thaumaleidae). 10 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 1 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 6 records from Untangling convoluted taxonomy of Chambriella Rego, Chubb & Pavanelli, 1999 (Cestoda: Proteocephalidae), with erection of Riggenbachiella n. g. and the description of a new species from pimelodid catfishes in the Neotropical Region. 260 records from Inventaire naturaliste de la commune de Papaichton (Guyane) : mission 2018. 1668 records from The ‘ red-tailed’ Lasioglossum (Dialictus) (Hymenoptera: Halictidae) of the western Nearctic. 188 records from Données de Mammifères marins. Mission Sanctuaire AGOA de 2012 à 2014. 852 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 167 records from Ten new species of Phyllodoce Lamarck, 1818 (Phyllodocidae, Annelida) from Brazil. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 1 records from Contributions to the taxonomy of Minixi Giordani Soika and Alphamenes Van der Vecht (Hymenoptera, Vespidae, Eumeninae), with an identification key to the species of the latter. 499 records from Chronicle of Nature - Phenology of Birds of Central Forest State Nature Biosphere Reserve. 14 records from The Goblin spider genus Xestaspis in Sri Lanka (Araneae: Oonopidae). 48 records from Bald Head Island 2004: Loggerhead Turtles (aggregated per 1-degree cell). 1 records from Deep-sea ascidians from Papua New Guinea. 19 records from Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae). 3 records from Indian Hecalina (Hemiptera: Cicadellidae: Deltocephalinae: Hecalini) with description of three new species. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 41676 records from Tagged Seal Location Data from SOGLOBEC. 333 records from Données naturalistes de Renaud PUISSAUVE. 310556 records from Dry Tortugas Reef Visual Census 2010. 527 records from Suivi ornithologique par IPA et IKA réalisés dans la Réserve nationale de l’Étang de Saint-Paul en 2012 et 2014. 26 records from Cetaceans sighted off the west coast of the South Island, New Zealand, Summer 1970. 194 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 1 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 9 records from Contribution to the Asian and Afrotropical species of the genus Dyschiriodes (Coleoptera: Carabidae: Scaritinae). 41 records from Ours 2008 présence Régulière Mailles_10km_LAEA Réseau Ours brun ONCFS. 1700 records from The Gibson spider collection. 56 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 8 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 112 records from Three new species of Oxypoda from Spain, Armenia, and Ukraine with notes on the fauna of Armenia (Coleoptera: Staphylinidae: Aleocharinae). 8 records from A new pelvic-less species of Melanorivulus Costa (Cyprinodontiformes: Cynolebiidae), with a discussion on the pelvic-fin absence in killifishes. 94 records from Truppenübungsplatz Panzerkaserne Böblingen. 1 records from The Calliphoridae (Diptera) of Armenia. 619 records from Réseaux écologiques/Trame verte et bleue. 14 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 2 records from Additions to the deep-sea echiuran (Echiura) fauna of the North-East Atlantic. 1 records from Happywhale - Harp Seal in North Pacific Ocean. 4 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 66164 records from Florida Keys Reef Visual Census 1996. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 18 records from Review of Scatimus Erichson (Coleoptera: Scarabaeidae) in Colombia with the description of a new species. 236480 records from Wild bees of Belgium. 54 records from Données du/de la naturaliste Villalta Rémi provenant de la base de donnée du SINP Île-de-France CETTIA. 22 records from Observations de tortues marines dans l'archipel de Saint-Pierre et Miquelon. 3 records from Review of the genus Pseudolathra Casey, 1905 (Coleoptera: Staphylinidae: Paederinae) of Réunion Island. 7 records from New species of the plesiomorphic genus Nixonia Masner (Hymenoptera, Platygastroidea, Platygastridae) from South Africa. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 344 records from Aspilanta new genus (Heliozelidae) specimen data. 3 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 181-1119. 549 records from If_Ecologie_Conseil_2017_12_18. 655 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hemiptera (ZUFMS-HEM). 1 records from Diagnostics and updated checklist of Oriental Pseudopostega (Opostegidae) including the matrona species group with a new, extralimital species discovered in the Mediterranean. 151 records from Taxonomic revision of West African cone snails (Gastropoda: Conidae) based upon mitogenomic studies: implications for conservation. 9740 records from Royal British Columbia Museum Entomology Collection. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 324 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 280 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 2 records from A new species of Macrothrix (Crustacea, Branchiopoda, Macrothricidae) from the Neotropics with description of the marthae-group. 13 records from Occurrence of mammalia relicts at site Großes Schulerloch. 8 records from A review of the Neotropical microcaddisfly genus Acostatrichia Mosely, 1939 with description of a new species from Brazil (Trichoptera: Hydroptilidae: Leucotrichiinae). 93 records from Journal of Hymenoptera Research. 66 records from Loggerheads in the Tyrrhenian Sea (aggregated per 1-degree cell). 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 8367 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 143 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 6 records from NZCS Invertebrates New Collection After 1987. 2985 records from Colección Entomológica CDMB. 1 records from Happywhale - Ringed Seal in North Atlantic Ocean. 16929 records from Lepidoptera (Specimens NRM). 993 records from ROC RSPB Farmland Species Survey Dataset. 2899 records from Biodiversidad asociada al gasoducto Paiva-Caracolí. 168 records from The cicadas (Hemiptera: Cicadidae) of Ecuador including the description of five new species, a new subtribe, four new synonymies, and fifteen new records. 198 records from Chronicle of Nature - Phenology of Birds of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 205 records from Wild boar sightings held by Andy Riches. 38 records from Bald Head Island 2007: Loggerhead Turtles (aggregated per 1-degree cell). 182049 records from Florida Keys Reef Visual Census 1999. 489 records from Caracterización bionómica de zonas de dragado y de afección de obras en la Ría de Ferrol. 42 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 69 records from First records and two new species of sipunculans (Sipuncula) from the Southern Mexican Pacific. 27799 records from Collection of saproxylic and xylobiont Beetles. 2 records from Two new species of Helicopsyche Siebold 1856 (Insecta: Trichoptera: Helicopsychidae) from Pará State, northern Brazil. 195 records from EDP Foz-Tua: Nocturnal Birds - Complementary Studies [2010]. 485557 records from The Danish Environmental Portal, species and habitats-database "Danmarks Miljøportals Naturdatabase". 9 records from Steinbock (1937) Turbellaria XIV. The fishery grounds near Alexandria. Notes and Memories of the Fisheries Directorate of Egypt, No. 25. 14 records from Review of East Palaearctic species of Sympycnus Loew, 1857, with a key to species. 2873 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología (Mexicanos). 3 records from Prosoglypta, a new remarkable genus from Vietnam (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 12866 records from MCP - Coleção de Abelhas. 31 records from Caracterización Ecológica de los Macroinvertebrados de las Fuentes Hídricas presentes en el Cerro Jánano. 19 records from Erhard Sopp. 720 records from Données du naturaliste Bussac Augustin provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Description of the previously unknown sexes in four West African Lycaenidae (Lepidoptera) with new data on their distribution. 135 records from Recensement des chiroptères 2012/2014 - Atlas de la biodiversité de Bordeaux Métropole. 306 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE293. 2 records from Charinus rocamadre (Amblypygi, Charinidae): description of the female, ultrastructure of the male and female gonopods, and mitochondrial DNA sequences. 983 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 4 records from New species and new geographical records in Disteniidae (Coleoptera, Chrysomeloidea) with revised keys to species of Novantinoe and American species of Distenia (Distenia). 181 records from Données du/de la naturaliste Beutin Sabine provenant de la base de donnée du SINP Île-de-France CETTIA. 1504 records from Woodmeadow Invertebrate Survey 2019. 43047 records from Données naturalistes de Pascal Dupont. 18 records from suivi du site Natura 2000 Carrière Saint Nicolas. 40 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 38 records from Faunal assemblage of sediment core GS7603-13. 310 records from Registros de macroinvertebrados acuáticos en un bosque seco del municipio de Honda. 2170 records from Inventaire des sangsues - détermination prélèvements de bureau d'études (qualité de l'eau) - Subvention UMS Patrinat. 105 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 1764 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 598 records from Monitoreo de la abundancia, riqueza y biodiversidad de aves del Santuario de Flora y Fauna Galeras en 2019. 2 records from A new species of the fishfly genus Neochauliodes van der Weele (Megaloptera Corydalidae) from India. 973 records from Freshwater Fishes of Bulgaria. 1082 records from Zootaxa. 2287 records from Colección de Anfibios. 5 records from USAKA Turtle Release Program (aggregated per 1-degree cell). 10973 records from NBMB Herps. 1 records from A new species-group of Clubiona Latreille, 1804 and descriptions of four new species from Borneo (Araneae, Clubionidae). 55 records from Ours 2007 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 17 records from (Table 2) Madreporarian corals collected in the Canary upwelling area. 199 records from Late Cretaceous and Cainozoic bathyal Ostracoda of DSDP Site 62-463 in the Central Pacific (Fig. 3). 2 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 3 records from A new species of Dohrnemesa from Brazil, with notes on the male of D. carvalhoi and on D. albuquerquei (Hemiptera: Heteroptera: Reduviidae: Emesinae). 12 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 2 records from Two new species of Hetereleotris (Perciformes: Gobiidae) from the Red Sea. 828 records from Données de la structure SNPN - Société Nationale de Protection de la nature provenant de la base de donnée du SINP Île-de-France CETTIA. 845 records from Alterra (NL) - Entomofauna inventory in arable fields Hoeksche Waard. 124 records from Données du/de la naturaliste jourdan christian provenant de la base de donnée du SINP Île-de-France CETTIA. 124 records from Occurrence of zoobenthos organisms in the sampled Central-Yakutian Lakes, Appendix 2-4. 147 records from Revision of the spider genus Hoplopholcus Kulczyński (Araneae, Pholcidae). 754 records from Programme ACT : Répartition Grive draine 2001 - 2005 Coordonnées GPS Lambert 93. 1783 records from Analysis of macrobenthos in the Southern Bight of the North Sea (1971-1972). 161 records from Interstitial and parasitic Platyhelminthes from the coast of the Seychelles in 1992 and 1993. 550 records from Colección de Referencia de Macroinvertebrados Bentónicos del Museo de Ciencias de la Universidad El Bosque. 10 records from Ostracoda abundance of Hole 32-306. 3 records from New species of karst-dwelling Pselaphinae from southwestern China (Coleoptera: Staphylinidae). 1 records from Morphological and molecular evidence of a new species of Melanochlamys (Gastropoda: Heterobranchia) from the Bohai Sea, China. 3281 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 3 records from Review of the Australian Signal Flies of the Genus Microepicausta (Diptera: Platystomatidae). 95950 records from Butterflies of Ireland. 66002 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 27220 records from Formidabel; Belgian Ants Database. 487 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 214 records from Caracterización de vertebrados terrestres en el Cerro Guadalupe, municipio de Manzanares. 14181 records from Index Site Surveys Data for Olympia Oysters, Ostrea lurida, in British Columbia – 2009 to 2017. 434 records from Aves de Caño Cristales, La Macarena, Meta. 11131 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 7 records from Abundance of nematoda in sediment profile M3/1_018 from the Iberian deep sea basin (Table 5). 116 records from Umgebung der Gesamtschule Hamburg-Winterhude. 3018 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 2617 records from Distribution patterns of subtidal macrobenthos in the Tsitsikamma National Park. 382 records from NHMO DNA Bank Other groups collection. 5 records from Sigambra sundarbanensis sp. nov. (Annelida, Pilargidae) from the Indian sector of Sundarbans Estuarine System, with remarks on parapodial glands. 1723 records from Revues diverses et littérature grise.. 99 records from (Table 4) Thecosomata in ODP Hole 134-831A. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 11 records from Barsine insolita, a new species from Indochina and India (Lepidoptera, Erebidae, Arctiinae). 8985 records from TPWD HARC Texas Coastal Fisheries Sabine Lake Gill Net. 42 records from DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 4 records from IMMS Ridley 9 (aggregated per 1-degree cell). 3 records from El género Aleuroparadoxus Quaintance y Baker 1914, con descripción de tres nuevas especies, nuevos registros y clave para las especies (Hemiptera: Aleyrodidae). 2 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 531 records from Expedición Providencia I - INVEMAR. 7 records from Description of lithologic section units of IODP Hole 325-M0050A. 2 records from Contribution to the tribe Pentoffiini (Cicadellidae: Evacanthinae) with descriptions of two new species and the male of Evanirvana aurea Hill, 1973. 463 records from Damselflies of the genus Argia (Odonata: Coenagrionidae) from Ecuador with descriptions of five new species. 3 records from Description of Bradinopyga konkanensis sp. nov. (Odonata: Anisoptera Libellulidae) from the coastal region of Maharashtra, India. 192291 records from University of Michigan Museum of Zoology, Division of Birds. 285 records from (Table 2) Fossil record of foraminifera and ostracoda from Muldsberg clay pit, north Germany. 249 records from Données naturalistes de AUNEAU Florent. 5 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 245 records from Coleoptera identified from the Borax Works, Norman Road site, Bexley, London. 1 records from Redescription of Chrysidea pumiloides Zimmermann, 1956, and description of three new species of Chrysidea from Madagascar (Hymenoptera: Chrysididae). 1 records from Taxonomic revision of the Afrotropical scarab beetle genus Cerhomalus Quedenfeldt, 1884 (Coleoptera: Scarabaeidae: Orphninae). 394 records from Collection Graptolithina fossil SMF. 1127 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 10 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 10 records from Talitrid amphipods from India, East Africa and the Red Sea (Amphipoda, Senticaudata, Talitroidea, Talitridae). 11 records from Suphisellus grossoi sp. n., a new burrowing water beetle from South America and notes on S. flavolineatus (Régimbart, 1889) and S. grammicus (Sharp, 1882) (Coleoptera: Noteridae). 2 records from Two new species of Neolindus from Peru and Venezuela (Coleoptera: Staphylinidae: Paederinae: Cylindroxystina). 14 records from Taxonomic and nomenclatorial revision within the Neotropical genera of the subtribe Odontocheilina W. Horn in a new sense— 18. Six Mexican and Central American species related to Odontocheila mexicana Laporte de Castelnau and O. ignita Chaudoir, with a description of O. potosiana sp. nov.. 5 records from The endemic Southern African genus Epirinus Dejean, 1833 (Coleoptera: Scarabaeidae: Scarabaeinae) revisited: five new species and two new synonyms. 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 48 records from Zoo Frankfurt. 203 records from Estrategia de conservación de grandes felinos en el departamento del Meta. 128 records from BIRDRACE Oostfreesland Bird-Lopers. 4 records from A new species of freshwater crab of the genus Phallangothelphusa Pretzmann, 1965, from the foothills of the Serranía Yariguíes of Colombia (Crustacea: Decapoda: Pseudothelphusidae). 49 records from DECAF - AUTEC Sperm Whales - Multiple Sensors - Samples. 63 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 1970 records from Dipterists Forum: Field Week 1981 (Kent). 625 records from Données araignées de Corse par Canard A., Rollard C., Villepoux O.. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 37929 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 19780 records from Eulachon migration bottom trawl surveys. 3 records from Two new species of freshwater crabs from the highlands of northern Uganda, East Africa and a redescription of Potamonautes amalerensis (Rathbun, 1935) stat. rev. from Mount Kadam (Brachyura: Potamoidea: Potamonautidae). 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 6301 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 97 records from Amphibiens filet/Marbotte-Ronval 2013. 83 records from Heavy minerals of sediment core PL94-64. 5 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 131125 records from Amphibiens et Reptiles de France (Enquête 2). 2100 records from Dolichopodidae of Portugal - dataset 2009-2018. 3319 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 16 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 2923 records from Données naturalistes d'Alain BERLY. 5 records from Two new species of Eumeninae from Iran (Hymenoptera: Vespidae). 27676 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 701 records from Données opportunistes. 183 records from (Table 6) Ostracod assemblages of sediment core 9409. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 368 records from Ring ouzel national sample survey in the UK in 1999. 1698 records from Red-throated diver national surveys in Scotland - raw data. 191 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 250 records from Inventaire et regroupement de données Natura 2000. 5 records from Two New Shallow-water Species of Agathotanais (Crustacea: Tanaidacea) from Japan. 12699 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 77 records from Suivi naturaliste du Parc du Peuple de l'Herbe. 486 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 2 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 1 records from Two new Afrotropical genera of Scatopsidae (Diptera). 56 records from Données du/de la naturaliste Goncalves Cristina provenant de la base de donnée du SINP Île-de-France CETTIA. 39 records from HRC CRC Small Vessel-Based Monitoring Surveys October 2009. 3689 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 2 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 26185 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 176 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 34 records from Oman 2008: Green Turtles of Masirah (aggregated per 1-degree cell). 6468 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 1490 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 300 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 1 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 31639 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 2067 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 99 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 15098 records from Collection Pisces SMF. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 11 records from NMML Harbor Porpoise Aerial Survey, Cook Inlet, 1991. 3 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 30 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 302 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 4 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 4 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 1553 records from University of Valencia cetacean surveys in the Spanish Mediterranean 2000-2003. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 65 records from Landschaftspflegehof (Berlin). 9 records from Bachpatenschaft Beeke. 201 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (4), 2011 - Données faune. 461 records from Données du/de la naturaliste Dodelin Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 341 records from SPC CoFish Invertebrates Observations Niue 2005. 14368 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 16 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 5366 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 91 records from Artenvielfalt auf den Elbwiesen (Dessau). 1 records from First Record of Holothuria (Cystipus) dura (Echinodermata: Holothuroidea) from Japan, with Notes on Locomotion. 10 records from Occurrence of mammalia relicts at site Meiendorf. 22124 records from Tachinid Recording Scheme - GB and Ireland records. 5 records from Thoridae (Crustacea: Decapoda) can penetrate the Abyss: a new species of Lebbeus from the Sea of Okhotsk, representing the deepest record of the family. 6 records from Five new species of Nazeris Fauvel in Guangxi, China (Coleoptera, Staphylinidae, Paederinae). 4379 records from Wild Bee Specimens from Blueberry and Raspberry Farms in the Champlain Valley, Vermont, USA. 11 records from A review of bat research in Thailand with eight new species records for the country. 5 records from Données naturalistes de Mikaël PAILLET. 4607 records from Données de type contact en Guadeloupe. 692 records from The Sphecid Wasps of the genus Cerceris L, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from the Palearctic Region (part II). (Hymenoptera, Apoidea, Crabronidae). 1 records from The Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) of Nepal. 79 records from New records of Ichneumonidae (Hymenoptera) for the Italian fauna. 1 records from Checklist of Benthic Cnidaria in the SW Atlantic Ocean (54 ºS- 56 ºS). 2 records from Description Of Etrocorema Belumensis Sp. N. From Royal Belum State Park, Perak, Malaysia. 7 records from New and little known species of Eumolpinae (Coleoptera: Chrysomelidae) from Northern Vietnam. 4 records from A new, uniquely patterned spiny eel (Teleostei: Mastacembelidae) from southern Borneo, Kalimantan Tengah, Indonesia. 1000 records from SEFSC Mid-Atlantic Tursiops Survey, 1995 3. 47 records from Galls on Beech Trees in Hainich, 2008. 2053 records from Atlas des Poissons et Crustacés d'eau douce de Guadeloupe. 6 records from New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae) from Colombia, with an identification key for all known species of the genus. 15 records from Three new species of Holoscolex (Clitellata, Glossoscolecidae) from the Gurupi Biological Reserve, last forest remnant of the Belém Endemism Area, Eastern Amazon. 3052 records from Inventario multitaxonómico del ANP Médanos de Samalayuca. 1037 records from Evaluación del estado actual de las poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en los municipios de Paz de Ariporo y Hato Corozal, Casanare. 8 records from A new species of Cetopsis from the Guiana Shield (Siluriformes: Cetopsidae: Cetopsinae). 122 records from Comunidad íctica del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 353 records from Annales de la Société Linnéenne de Maine-et-Loire. 130 records from New species of Ilanga (Gastropoda: Trochoidea: Solariellidae) from the Indo-West Pacific. 116 records from Données de Mammifères marins dans les TAAF et autres territoires issues de la bibliographies. Compte cardobs 1007 (Trudelle). 7 records from Diversification in the mountains: a generic reappraisal of the Western Ghats endemic gecko genus Dravidogecko Smith, 1933 (Squamata: Gekkonidae) with descriptions of six new species. 500 records from Chronicle of Nature - Phenology of Insects of Pechoro-Ilych State Nature Reserve. 53 records from Données malacologiques continentales de Julien Ryelandt (CORSE 2017). 1 records from Macrochelid mites (Mesostigmata: Macrochelidae) from São Paulo state, Brazil, with description of a new species of Macrocheles. 12395 records from Insectes Hétéroptères Mirides de France. 23 records from The genus Leucophenga (Diptera, Drosophilidae), part VII: the subpollinosa species group from China, with morphological and molecular evidence. 1 records from Happywhale - Long-finned Pilot Whale in North Pacific Ocean. 1538 records from Données du naturaliste ROCHAT Didier provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Taxonomic notes on the tribe Dryptini Bonelli, 1810 with description of a new genus and species from China (Coleoptera: Carabidae: Dryptini). 354 records from Programme ACT : Répartition Caille des blés 2000 - 2004 Coordonnées GPS Lambert 93. 33 records from Pollen analysis of sediment core GeoB6518-1. 3 records from Three new taxa of Noctuidae from China (Lepidoptera: Noctuidae). 11 records from Description of lithologic section units of IODP Hole 325-M0055A. 94 records from Quarrendorfer Landschaftsschutzgebiet. 108 records from NEFSC Deepwater Marine Mammal 2002. 168 records from Registros de quirópteros de tres localidades del caribe colombiano. 137 records from Lynx 2009 présence Occasionnelle Mailles_10km_LAEA Réseau Loup-Lynx ONCFS. 7 records from Estonian University of Life Sciences Institute of Agricultural and Environmental Sciences Mycological Herbarium. 10 records from New plant associations for adults of some species of Acmaeodera Eschscholtz (Coleoptera: Buprestidae) occurring in the western United States. 6 records from Out on a limb: novel morphology and position on appendages of two new genera and three new species of ectoparasitic isopods (Epicaridea: Dajidae) infesting isopod and decapod hosts. 14 records from BMHS Crustacean Collection. 27 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 1 records from Happywhale - Antarctic Fur Seal in Indian Ocean. 42 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 55 records from Données naturalistes de Pauline BALDUCCI. 16 records from PROJET DE CONSTRUCTION D’UNE ROUTE DE TRANSPORT DES MINERAIS DE BAUXITE DE GAC: EIES, inventaire des amphibiens (CESP2016-022). 135 records from DIBA-Parc del Montnegre i el Corredor. 165572 records from University of Tartu Natural History Museum and Botanical Garden Zooloogical Collections. 21 records from Caracterización de la epifauna y macrobentos (0-800 m) de Isla Cayo Serranilla y Áreas aledañas: Equinodermos primera fase 2017 - Proyecto Colombia Bio. 194 records from Données du/de la naturaliste LELARDOUX LOIC provenant de la base de donnée du SINP Île-de-France CETTIA. 4755 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 1 records from Re-description of Grammapsychops lebedevi Martynova, 1954 (Neuroptera: Psychopsidae) with notes on the Late Cretaceous psychopsoids. 1124 records from JRS Wetands data Rwanda, 2019. 2 records from A new species of Polietina (Diptera: Muscidae) from South America, with an updated phylogeny of the genus and a review of species’ identity in GenBank. 2 records from On species of the genus Macrosaldula (Hemiptera: Heteroptera: Saldidae) of the Palaearctic Region, with description of M. graziae sp. nov.. 15926 records from Muséum_de_Toulon_et_du_Var_2017_12_18. 1 records from Review of the genus Bythonia Oman 1936 with description of a new species and new record from Venezuela (Hemiptera, Cicadellidae, Iassinae). 17 records from Description of lithologic section units of IODP Hole 325-M0043A. 7 records from Grundwasserlebensraum im Englischen Garten (München). 208 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 2 records from Dilatapalochrus gen. nov. - a new species and a new genus of soft-winged flower beetle of the tribe Apalochrini (Coleoptera: Malachiidae) from East Africa. 3473 records from Fish Collection of National Museum, Philippines. 830 records from Invertebrados del Parque Nacional Arrecife Puerto Morelos. 1 records from A new species of the swimming crab genus, Laleonectes Manning & Chace, 1990 (Crustacea: Brachyura: Portunidae), from the western Indian Ocean. 3 records from Description of a new species of the Rhinolophus trifoliatus-group (Chiroptera: Rhinolophidae) from Southeast Asia. 19 records from Nesting biology and distribution of Stenancistrocerus (Paratropancistrocerus) obstrictus (Morawitz, 1895) (Hymenoptera: Vespidae: Eumeninae). 753 records from Colección de insectos de importancia médica del Instituto Nacional de Salud - Ceratopogonidae. 1009 records from Données naturalistes de Daniel PAVON. 19 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (ANONAU). 1431 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 3 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 59 records from Seabird and cetacean sightings from Cruise SY002 of RV Shoyo Maru, Tropical Atlantic Ocean, Oct. 2000. 434 records from A revision of the minor species group in the millipede genus Nannaria Chamberlin, 1918 (Diplopoda, Polydesmida, Xystodesmidae). 60 records from Caracterización de la fauna reptiliana asociada a la cuenca del río Atrato, para el estudio de su navegabilidad, Quibdó - Chocó, 2012. 1 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 9 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 302768 records from Estonian Nature Observations Database. 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 52 records from Description of three new velvet geckos (Diplodactylidae: Oedura) from inland eastern Australia, and redescription of Oedura monilis De Vis. 5 records from Genome sequencing reveals extraordinary cephalic horns in the Madagascan dung beetle genus Helictopleurus (Coleoptera, Scarabaeinae): insight from a revision of fungicola species group. 7 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 589 records from Birds (NMNO-BI). 11686 records from NCSM Mammalogy Collection. 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 24 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 225 records from Nivå Bay species list, Zealand, Denmark. 91645 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 2 records from New Vietnamese Species Of The Genus Flavoperla Chu (Plecoptera: Perlidae). 7 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 168856 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 6 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 17 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 3 records from Eleven new species and a new country rec
Keywords: GBIF; biodiversity; species occurrences